Highly sensitive lateral flow immunoassays targeting PirA and PirB toxins for early on-site diagnosis of AHPND in shrimp - Chia-Chun Hsiao; You-Shan Cai; Shin-Yu Chou; Hung-Yun Lin; Shao-Chieh Yen; Han-Jia Lin; Shih-Chung Chang (Aquaculture, 2027)

Simultaneous LC-MS/MS screening of 222 drugs of abuse in eight solid food matrices using a unified QuEChERS-Based approach - Eunbin Ryu; Jae Ui Park; Jin Ah Lee; Sangeun Lee; Wonhee Koo; Yoon Hee Lee; Jungmin Shin; Jihyun Lee; Jaewoo Song; Hangji Ok; Mi Jeong Oh; Jae-Sung Pyo; et al. (Regulatory Toxicology and Pharmacology, 2026)

Stable and reusable hydrophobic biochar–alginate–cellulose beads for efficient microplastic removal in aqueous systems - Hang Vo-Minh Nguyen; Hyun-Rak Son; Ji-Hyun Han; Minh Chau Dao; Hyun-Sang Shin (Journal of Water Process Engineering, 2026)

DataNet: linking multi-faceted building energy datasets for effective performance analysis at scale - Hye-Gi Kim; Hyery Shin; Han-Gyeong Chu; Dong Hyuk Yi; Sang-Lin Park; Doosung Kim; Hyunwoo Lim; Sungmin Yoon; Eui-Jong Kim; Jaewan Joe; Sunsook Kim; Hyeunguk Ahn; et al. (Energy and Buildings, 2026)

Tiers, thresholds, and trade-offs: Policy design for U.S. 45V hydrogen credits - Woojae Shin; Han Ho Song (Energy Policy, 2026)

Highly selective solar CO2 conversion into ethanol over metal-free sulfonated g-C3N4/nitrogen doped reduced graphene oxide hybrid photocatalyst - Sachin G. Ghugal; Amol U. Pawar; Park Kyoung Mo; Poonchi Sivasankaran Ramesh; Harish Reddy Inta; Sanjeev Gupta; Sung-hoon Oh; Muhammad Zaeem Azam Khan; Young Seok Son; Hyunchul Shin; Hongxian Han; Young Soo Kang (Chemical Engineering Journal, 2026)

Decoupled sulfur redox pathways governed by initial chemical states in all-solid-state lithium–sulfur batteries - Eunbyoul Lee; Jonghyun Han; Jiwon Jeong; Hamin Choi; Eunchae Seo; Tae Joo Shin; Kyung Yoon Chung (Chemical Engineering Journal, 2026)

Ultrastable γ-Al2O3 catalyst co-doped with zinc and phosphate for stable CF4 hydrolysis over 3700 h - Eun-Han Lee; Won-Seob Cho; Dongmin Jeon; Chan-Woo Lee; Yonghoon Cho; Sungtak Kim; Jaehyun Cho; Hansung Kim; Shin-Kun Ryi (Chemical Engineering Journal, 2026)

Heterocyclic aromatic nitrogen carbon dots as sprayable fluorescent probes for the identification of real chemical warfare agents - Hanseung Kim; Hyeonho Jeong; Byeongjun Jeon; Myeong Seo Cha; Donghyeon Kim; Yanamala Poojitha; Soobin Han; Yonghyeon Park; Jungjoo Lee; Moein Safarkhani; Fahimeh Taghavimandi; Young-Su Jeong; et al. (Chemical Engineering Journal, 2026)

pH changes differently affect carbonic anhydrases (Ap-CAs) transcriptions in the marine toxic dinoflagellate Alexandrium pacificum - Han-Sol Kim; Jeongmin Shin; Taehee Kim; Jang-Seu Ki (Marine Environmental Research, 2026)

Contrasting growth phase-dependent microbiota dynamics between dinoflagellates and diatoms - Joo-Hwan Kim; Jin Ho Kim; Zhun Li; Jang-Seu Ki; Hyeon Ho Shin; Young Kyun Lim; Seung Ho Baek; Pengbin Wang; Ro Young Park; Soo Hwan Jhin; Myung-Soo Han; Bum Soo Park (Harmful Algae, 2026)

Role of boron doping in bulk and surface structural regulation of cobalt-free high-nickel layered cathodes - Seung U. Chun; Jae Hyeon Choi; Eun-Jung Shin; Kyoung Sun Kim; Han-Koo Lee; Won Gi Hong; Hyungsub Kim; Young-Sang Yu; Gi Dae Park; Sang Mun Jeong (Chemical Engineering Journal, 2026)

Dielectric oligonucleotide fragments enable ultralow threshold photomultiplication in infrared quantum dot photodetectors - Yongnam Ahn; Jinwoo Shin; Woo Hyuk Jung; Yong Ho Cho; Minjung Yang; In-Suh Lee; Jaewoo Jeong; Taeho Han; Seoryeon Jeong; Jin Ah Lee; Chae Hyeong Ha; Yoon Jang Chung; et al. (Chemical Engineering Journal, 2026)

Liquid metal particles enabled ultrahigh isotropic thermal conductivity in soft thermal interface materials for biochips packaging - Yoonsu Lee; Sangkeun Oh; Yu-Jin Song; Ji-un Jang; Joo Hyung Lee; Seoyeon Won; Joohwan Yoo; Youngho Eom; Han-Kyun Shin; Huanan Zhang; Qian Zhou; Shi Hyeong Kim; et al. (Chemical Engineering Journal, 2026)

Exercise attenuates cisplatin-induced anorexia-cachexia via modulation of hypothalamic inflammation and orexigenic signaling - Se Hwan Park; Jeong Rim Ko; Chang Shin Yoon; Nam Mi Park; Maria Victoria Faith V. Garcia; Hyung Kyu Kim; Jin Han (European Journal of Applied Physiology, 2026)

Age-associated DNA methylation patterns in mouse blood and tail: feasibility of tissue-specific epigenetic clock development - Jiwon Shin; Seungmin Song; Yerim Han; Jieun Lyu; Yoon Jung Park (GeroScience, 2026)

Corrigendum to “Heavy metal-induced proteomic profiles associated with disease risk in environmentally vulnerable populations” [J Hazard Mater 511 (2026) 142267] - Min Heo; Sora Mun; Nam-Eun Kim; Hyeongyu Shin; Ah Ra Do; Jeeyoung Kim; Jung-Yeon Kwon; Sujin Seo; Hyein Han; Yong Min Cho; Young-Seoub Hong; Hee-Gyoo Kang; et al. (Journal of Hazardous Materials, 2026)

Curvature extraction algorithm for seismic image and velocity model evaluation: Application to CMP and angle gathers - Soohwan Park; Seunghoon Han; Jungkyun Shin; Youngseo Kim; Yongchae Cho (Journal of Applied Geophysics, 2026)

Effect of Level of Posterosuperior Cuff Tear Severity on Joint Contact Mechanics in Reverse Total Shoulder Arthroplasty: A Simulation Study - Donghwan Lee; Joo Han Oh; Jinkyu Lee; Sungwook Jung; Jungsung Kim; Namkeun Kim; Choongsoo S. Shin (Annals of Biomedical Engineering, 2026)

Emerging metabolic hormone therapeutics for metabolic dysfunction-associated steatohepatitis: incretin-based drugs, fibroblast growth factor analogs, and liver-targeting strategies - Sukwoo Han; Jaehee Shin; Jae Cheon Kim; Dong Hee Na (Journal of Pharmaceutical Investigation, 2026)
Background As the prevalence of metabolic dysfunction-associated steatohepatitis (MASH) continues to rise, drug development has accelerated, with growing interest in therapeutic strategies that harness metabolic hormones. Metabolic hormone-based approaches, particularly those originally developed for obesity and diabetes, have shown potential to mitigate MASH. Notably, the glucagon-like peptide-1 receptor (GLP-1R) agonist semaglutide received accelerated approval for MASH in 2025. In addition, GLP-1R-based multi-agonists and candidates leveraging the metabolic actions of fibroblast growth factor (FGF) 21 are in active clinical development for liver disease. Area covered This review provides an overview of metabolic hormone-based therapies, including incretin-based drugs and FGF analogs, that are currently under clinical development for MASH. It also discusses liver-targeting strategies to achieve selective hepatic delivery, which may vary according to the expression of liver-specific receptors and fibrosis degree. Expert opinion Within the MASH therapeutic landscape, incretin-based therapies are evolving from GLP-1R mono-agonist to multi-agonist approaches that aim to combine weight loss-mediated benefits with mechanisms that directly modulate hepatic lipid handling and inflammation. Moreover, the therapeutic actions of metabolic hormones in MASH, together with the expression profiles of their corresponding receptors, play a critical role in determining targeting strategies. Stage-specific and liver-selective delivery strategies will likely distinguish next-generation candidates. This review summarizes the pharmacological mechanisms and delivery strategies of each agent class and further explores these receptors as potential targets to inform the development of precision therapeutic approaches.

Nutri-cereals as functional foods and their pharmacological intervention in gastroprotection and regulation of diabetes - Gitishree Das; Rajat Nath; Anupam Das Talukdar; Han-Seung Shin; Jayanta Kumar Patra (PharmaNutrition, 2026)

Heavy metal-induced proteomic profiles associated with disease risk in environmentally vulnerable populations - Min Heo; Sora Mun; Nam-Eun Kim; Hyeongyu Shin; Ah Ra Do; Jeeyoung Kim; Jung-Yeon Kwon; Sujin Seo; Hyein Han; Yong Min Cho; Young-Seoub Hong; Hee-Gyoo Kang; et al. (Journal of Hazardous Materials, 2026)

Correction: A 3D Printed Poly(ε-caprolactone)-Collagen Hybrid Mesh (TissueDerm) for Breast Reconstruction after Mastectomy in a Pig Model - Kyu-Sik Shim; Han-Saem Jo; Shin Hyun Kim; Dohyun Kim; Yong-Kyu Park; Da-Hye Ryu; Won-Jai Lee; Tai-Suk Roh; Wooyeol Baek (Tissue Engineering and Regenerative Medicine, 2026)

Evaluation of fluid behavior and turnover in aquaculture tanks using CFD and transient temperature fields - Seung-Jun Lee; Hyeon Geun Shin; Kyung-Nam Han (Aquacultural Engineering, 2026)

Association between obesity and subsequent risk of myasthenia gravis: a nationwide population-based cohort study - Soonwook Kwon; Ye Bin Park; Kyung-Do Han; Yeon Hak Chung; Eun Bin Cho; Dong Wook Shin; Ju-Hong Min (Acta Neurologica Belgica, 2026)
Background Obesity causes a pro-inflammatory environment and is an established risk factor for a variety of autoimmune diseases. However, the association with the subsequent risk of myasthenia gravis (MG) was unclear. Methods This nationwide cohort study evaluated 3,937,214 adults over 20 years old, using data from the Korean National Health Insurance Service. Participants were categorized by body mass index (BMI) into underweight (BMI Results During about 10-year follow-up, 799 individuals developed MG (mean age 47.3 years old [SD, 14.02 years], male 54.6%, and BMI ≥ 25 kg/m 2 32.6%). The incidence rate was highest in the obese class II group (3.39/100,000 person-years). Obese class I (aHR 1.20, 95% CI 1.00–1.43) and class II (aHR 1.88, 95% CI 1.37–2.56) groups demonstrated significantly elevated MG risks compared to the normal BMI group. In subgroup analyses, underweight males had a notably increased risk (aHR 2.16, 95% CI 1.24–3.78). Conclusion Obesity has an association with an increased risk of subsequent MG, suggesting a potential risk factor of MG. Further studies are needed to elucidate the association between obesity and MG.

Evaluation of seasonal variations in energy sources and trophic positions of Calanus sinicus and Euphausia pacifica in the central-eastern Yellow Sea using bulk and compound-specific stable isotope analyses - Jiseung Kang; Yeonjung Lee; Dong Han Choi; Jae Hoon Noh; Howon Lee; Hyung-Ku Kang; Garam Kim; Kongtae Ra; Myung Jin Hyun; Won Seok Yang; JongSeok Won; Bohyung Choi; et al. (Marine Pollution Bulletin, 2026)

An in vitro model of bleomycin-induced epithelial injury using stem cell-derived alveolar type 2 epithelial cells - Yubin Han; Ha Ryong Kim; Jun Woo Kim; Tae Hwan Shin; Hyung Sik Kim; Kyu Hyuck Chung; Yong Joo Park (Toxicology Letters, 2026)

Editor's Note to “Inhibiting bacterial biofilm formation by stimulating c-di-GMP regulation using citrus peel extract from Jeju Island” [Sci. Total Environ., 872, (2023), 162180] - Han-Shin Kim; So-Young Ham; Hwa-Soo Ryoo; Hee-Deung Park; Jeong-Hoon Park (Science of The Total Environment, 2026)

Dose-dependent cerebral metabolic impairment in a swine model of carbon monoxide poisoning - Alistair Lewis; Rodrigo M. Forti; Tiffany S. Ko; John C. Greenwood; Matthew Kelly; Frances S. Shofer; Shih-Han Kao; Samuel S. Shin; Devesh Bungatavula; Mckenna Mason; Jonathan Starr; Johannes K. Ehinger; et al. (NeuroToxicology, 2026)

Hierarchical surface energy alignment in bio-oil–infused ionic liquids for enhanced lubrication - Nur Aisya Affrina Mohamed Ariffin; Shin Ying Foong; Chiew Tin Lee; William Woei Fong Chong; Su Shiung Lam; Jo-Han Ng; Cheng Tung Chong; Arunkumar Thirugnanasambandam (Fuel, 2026)

Nickel-incorporated core–shell porous organic polymer for green conversion of levulinic acid to γ-valerolactone - Yujin Choi; Hyug Hee Han; Chaewon Shin; Jung-Hyeok Park; Joo Yeon Han; Chang-Ha Lee; Seenu Ravi; Youn-Sang Bae (Chemical Engineering Journal, 2026)

Near-infrared light–responsive implantable module integrated into glaucoma drainage device for controlled antifibrotic drug therapy - Chang Hee Min; Young In Shin; Han Bi Ji; Soo Bin Yoon; Yeonseo Kim; Cho Rim Kim; Jae Hoon Han; Min Ji Kim; Myung Ju Kim; Eun Jung Kwon; Young Kook Kim; Ki Ho Park; et al. (Chemical Engineering Journal, 2026)

Evaluation of Metal(loid) Immobilization and Lettuce (Lactuca Sativa L.) Growth in Soil Treated with Biochar and Modified Biochar with Iron Phosphate - Han Na Kim; Seung Jun Lee; Su Kyeong Shin; Jeong Yeon Kim; Ye Eun Lee; Jin Hee Park (Water, Air, & Soil Pollution, 2026)

Quantifying the joint effects of soil salinity and fertility on rice growth and yield variability in coastal paddies of southwestern Korea - Seo-Woo Park; Nuri Baek; Se-In Lee; Eun-Seo Shin; Hyun-Jin Park; Han-Yong Kim; Kyo-Suk Lee; Kwang-Seung Lee; Nurgul Kitir Sen; Woo-Jung Choi (Journal of Soils and Sediments, 2026)

Comparison between genomic alterations in mouse, pig, and human through whole-genome sequencing - Geon Hue Bae; Seong Gyu Kwon; Jeong-Woo Choi; Joo Hee Hong; CheolMin Jeon; Areum Cho; JaeEun Shin; Mee Sook Jun; Man-Hoon Han; Seock Hwan Choi; Ji Won Oh (Journal of Genetics, 2026)

MUDENG, a component of adaptor complex 5, mediates TRAIL- and TMZ-triggered apoptosis in glioblastoma (GBM) via multiple pathways - Juhyun Shin; Yoon-Mi Lee; SooHyun Jung; Sumin Han; Arti Nile; Su-Jin Kim; Sang-Won Lee; Jae-wook Oh (Apoptosis, 2026)

Discovering anti-obesity blue food compounds via combined deep learning and in silico approaches - Seo Hyun Shin; Eunseok Oh; Chanyoon Park; Seung Man Oh; Hee Jeong Hwang; Jeong Yun You; Hyeri Ryu; Gihyun Hur; Ji Woo Kim; Jung Han Yoon Park; Eun Roh; Heonjoong Kang; et al. (Molecular Diversity, 2026)
Blue foods, such as fish and aquatic sources, are rich in bioactive compounds with potential health benefits, including anti-obesity effects. AMPK, a key regulator of energy homeostasis and adipogenesis, plays a vital role in combating obesity by inhibiting adipocyte differentiation. This study aimed to identify natural AMPK activators from underexplored blue foods using a deep learning-based compound-protein interaction (CPI) prediction model that incorporates both local and global features of proteins and compounds. Local and global molecular characteristics were systematically represented using sequence-based encodings, molecular fingerprints, and protein descriptors to enhance the model’s ability to capture diverse biochemical relationships. The deep learning framework integrated these multimodal features through neural network modules to predict potential compound–protein interactions. In silico molecular docking was performed to refine the predicted interactions, leading to the identification of 94 top-scoring compounds with strong binding affinity toward AMPK. In vitro validation of five commercially available compounds confirmed anti-obesity activity. Notably, cyclo(Pro-Val) from Ulva pertusa , activated AMPK and modulated key adipogenic markers, suggesting its potential as a natural AMPK activator for obesity prevention and the feasibility of AI-driven screening for marine bioactives.

First record of Pseudadenoides kofoidii, a marine sand-dwelling dinoflagellate, from Geoje Island, Korea: morphology, phylogeny, and growth and fatty acid content under different temperature conditions - Da Bin Choi; Minseok Jeong; Zhun Li; Kyong Ha Han; Minjae Kim; Pung-Guk Jang; Joo-Eun Woo; Joo Yeon Youn; Bum Soo Park; Jin Ho Kim; Joo-Hwan Kim; Hyeon Ho Shin (Algae, 2026)
To clarify an unidentified marine sand-dwelling dinoflagellate isolated from samples collected at a sandy beach of Geoje Island, Korea, its morphology and molecular phylogeny based on the small and partial large subunit rRNA gene sequences were examined. In addition, growth responses and fatty acid content of the isolate under different temperature conditions were investigated to assess its physiological traits and aquaculture potential. Cells were 26.3–41.5 μm long (34.8 ± 3.6 μm) and 19.8–40.8 μm deep (28.9 ± 4.8 μm), and a nucleus located in the dorsal half of the cell and pyrenoid surrounded by a starch sheath were observed. Scanning electron microscope observations revealed that the cells were characterized by a lack of precingular plates, scattered thecal pores, a single flagellar pore and a shallow anterior cingulum. One or two pores were present on the plate 3p, and one pore was consistently observed on plate 4p. The phylogenetic analyses revealed that the Korean isolate can be identified as Pseudadenoides kofoidii that has not previously been described in Korean coastal area. In the growth experiments, the isolate appeared to prefer moderate temperatures (15 and 20°C) rather than higher temperature (25°C). Although this species exhibited temperature-dependent variation in docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) production, P. kofoidii maintained remarkably high levels of DHA and EPA in its fatty acid composition (>42% of total fatty acids), highlighting its potential as a promising marine source of fatty acids for aquaculture applications.

A Next-Generation Recombinant Botulinum Toxin With Enhanced Activity and Longer Duration of Action - Mi Seon Shin; Laon Kim; Jae Yoon Byun; Hee Won Min; Su Hyeok Kim; Ui Beom Park; Deu John M Cruz; Seongsung Kwak; Kook-Han Kim (Toxicon, 2026)

Comparative microbial responses and degradation characteristics of petroleum-based and biodegradable chainsaw lubricants in forest soils impacted by timber harvesting - Ikhyun Kim; Jaewon Seo; Yongsuk Kim; Keumchul Shin; Sang-Kyun Han; Byoungkoo Choi (Journal of Hazardous Materials, 2026)

Deactivation of Colletotrichum acutatum and Colletotrichum gloeosporioides by novel cylindrical dielectric barrier discharge plasma: Maintaining biochemical composition in strawberry by in-vitro and in-vivo - Sekar Ashokkumar; Roshani Dahal; Yung Oh Shin; Han Sup Uhm; Jang Sick Park; Young-Chul Lee; Eun Ha Choi (Food Control, 2026)

Hybrid graphite anodes with vertical nanochannels for high-capacity and long-cycle lithium-ion batteries - Kyungjun Kim; Hwijoo Lee; Hong Rim Shin; Seongsoo Park; Jaeyeon Bang; Daehun Han; Sungji Kim; Ilyoung Choi; Youngugk Kim; Janghyuk Moon; Jong-Won Lee; Sang-Min Lee (Chemical Engineering Journal, 2026)

Large-scale protonic ceramic electrochemical cells fabricated by inkjet printing - Sung Min Kang; Yoon Seong Kim; Kyung Chan Min; Sun Beom Kim; Dongwook Shin; Wonyoung Lee; Jongsup Hong; Gwon Deok Han; Joon Hyung Shim (Chemical Engineering Journal, 2026)

Exosomal microRNA profiling reveals candidate biomarkers and regulatory signatures associated with paratuberculosis disease status in goats - Eun-Yeong Bok; Tae Yoon Kim; Sang-Young Seo; Han-Gyu Lee; Young-Hun Jung; Seong Hwan Bae; Nam Su Oh; Tae Jin Cho; Hyeon Woo Park; Eui Cheol Shin; Jae Kyeom Kim (The Veterinary Journal, 2026)

Subchronic oral toxicity and genotoxicity of Aurantii Fructus Immaturus water extract - So-Young An; Si-Whan Song; Hyun-Suk Heo; Chang-Wok Park; Min-Sub Kim; Woo-Joo Lee; Yoo-Jin Park; Jae-Ho Shin; Beom Seok Han; Wan-Seob Cho (Regulatory Toxicology and Pharmacology, 2026)

Quantitative evaluation of hydrogeologic properties controlling field-scale DNAPL contamination across porous and fractured media - Taehoon Kim; Weon Shik Han; Jehyun Shin; Seonkyoo Yoon; Peter K. Kang; Woojong Yang; Seunghak Lee (Journal of Hydrology, 2026)

Antiviral potential and mode of action of Metarhizium pinghaense 15R-derived polysaccharide against baculovirus - Jiwon Jang; Gui Hwan Han; Seong Hun Im; Jeong Won Kim; Soo Dong Woo; Tae Young Shin (Journal of Invertebrate Pathology, 2026)

Development of a web-based No coding machine learning platform for hydrology and environmental management - MoolML - Sangjoon Bak; Jeongho Han; Gwanjae Lee; Naehyeon Nam; Joo Hyun Bae; Yeonji Jeong; Hyungjin Shin; Kyoung Jae Lim; Seoro Lee (Environmental Modelling & Software, 2026)

Performance improvement of solar-assisted hybrid water-source heat pumps through multi-objective system control optimization - Changho Han; Jinyoung Kim; Dong Soo Jang; Hyun Ho Shin; Yongchan Kim (Energy and Buildings, 2026)

Aqueous LC-MS/MS quantification of α-/β-nicotinamide mononucleotide in dietary supplements using a pentabromophenyl column - Chng Sze Hoei; Nian-Hua Wu; Chao-Ming Tsen; Ping-Wei Sun; Han-Wei Chang; Shin-Yuan Wang; Hung-Yu Lin (Analytica Chimica Acta, 2026)

A Study on an Extrapolation Method for the Propulsive Performance of the Pumpjet Propulsor of a Submarine - Woo-Seok Jin; Moon-Chan Kim; Jin-Wook Kim; Il-Ryong Park; Han-Shin Seol (Journal of Marine Science and Engineering, 2026)
Accurately predicting the full-scale performance of submarines is challenging due to their complex propulsor systems and limited sea-trial information. This study investigated a full-scale extrapolation method from model tests for a submarine pumpjet propulsor, as a reliable method has not been established. Three extrapolation methods from ITTC reports were reviewed and applied to the pumpjet propulsor of the SUBOFF submarine, then compared with full-scale CFD results. Among the reviewed methods (Methods 1 to 3), Method 3, which separates the duct and stator as appendages of the hull and includes the entire pumpjet in the POW test but uses only the rotor’s force, was the most reasonable, but showed significant differences from the calculated results, especially in the PD. This study proposed a modified Method 3, improving it by adopting the continuity theory to predict the oncoming velocity of a rotor and by applying a correction factor for the drag of the duct and stator. The modified PJP extrapolation method 3 showed excellent agreement with the full-scale CFD analysis results across all propulsion coefficients, with a minimal error of 0.45% for PD. Despite the structural differences in PJPs, such as stators and longer ducts, velocity changes are dominated by the duct’s internal area. Therefore, the proposed extrapolation method is equally applicable to general ducted propellers.

Biofouling mitigation in cathodic electrochemical filtration via combined sublethal oxidative stress and electrostatic repulsion - Jeong Hoon Lee; Han-Shin Kim; Eun-Tae Yun; So-Young Ham; Peng-Fei Sun; Hwa-Soo Ryoo; Hee-Deung Park (Water Research, 2026)

Photocatalytic ethylene scavenging by chitosan/gelatin packaging films loaded with TiO2-functionalized bismuth metal organic frameworks for postharvest preservation of fruits - Zohreh Riahi; Ajahar Khan; Su Jung Hong; Jong-Whan Rhim; Gye Hwa Shin; Sea C. Min; Sanghee Han; Seok-Geun Lee; Jun Tae Kim (Food Chemistry, 2026)

Differential toxicity of polyhexamethylene guanidine phosphate administered through intravenous injection and intratracheal instillation in Sprague-Dawley rats - Se-Woong Park; In-Sik Shin; Sung-Hwan Kim; Han Na Suh (Food and Chemical Toxicology, 2026)

Multi-scale computational approach to understand plasma assisted sulfidation for growth mechanism of MoS2 - Jinill Cho; Tae-Hyun Kim; Nayoon Kang; Jinhyoung Lee; Gunhoo Woo; Hyelim Shin; Sujeong Han; Geon Woong Eom; Hyeong-U Kim; Chanho Park; Hyunbin Choi; Keunseok Kim; et al. (Chemical Engineering Journal, 2026)

A 3D Printed Poly(ε-caprolactone)-Collagen Hybrid Mesh (TissueDerm) for Breast Reconstruction after Mastectomy in a Pig Model - Kyu-Sik Shim; Han-Saem Jo; Shin Hyun Kim; Dohyun Kim; Yong-Kyu Park; Da-Hye Ryu; Won-Jai Lee; Tai-Suk Roh; Wooyeol Baek (Tissue Engineering and Regenerative Medicine, 2026)

Bisphenol AF induces mouse spermatogonia apoptosis via reactive oxygen species-mediated Beclin-1 cleavage - Hyo Jin Gu; Gil Un Han; Seul Gi Kim; Sung-Hwan Moon; Seung Hee Shin; Buom-Yong Ryu (Toxicological Research, 2026)

An improved Slepian method for mitigating signal leakage in Greenland ice sheet mass variation estimation - Zehao Gong; Jiangjun Ran; Shin-Chan Han; Natthachet Tangdamrongsub; Zhengwen Yan (Journal of Geodesy, 2026)

Comprehensive in silico analysis of Acinetobacter isolates from South Korea reveals genomic diversity, antimicrobial resistance, virulence factors, and evolutionary dynamics - Md Minarul Islam; Kyudong Han; Kyungho Woo; Woo Shik Shin; Man Hwan Oh (Genes & Genomics, 2026)

The role of Alu elements in causing BRCA1 structural variation and breast cancer susceptibility - Minjae Yu; Dahee Jo; Wonseok Shin; Kyudong Han (Genes & Genomics, 2026)

Hahella aquimaris sp. nov., a bacterium producing prodigiosin isolated from aquaculture seawater - Seung Yeol Shin; Hyomin Seo; Yihyun Jeon; Heeyoung Kang; Hye Seon Song; Song-Ih Han; Jaeho Song (Antonie van Leeuwenhoek, 2026)

Integrated environmental assessment framework for evaluating and managing nitrogen contamination in complex fractured aquifer systems - Soonyoung Yu; Ho-Rim Kim; Jehyun Shin; Seong-Taek Yun; Han-Suk Kim; Hyun-ji Kang (Journal of Environmental Management, 2025)

Development of ccombodies identify WSSV VP28 protein - Sung Ok Shin; Rodelas-Angelia Abigail Joy; Angelia Mark Rickar; Han-Ching Wang; Seung Beom Hong; Tae Sung Jung (Fish & Shellfish Immunology, 2025)

Uncovering AphBvp-mediated regulation of PirAvp/PirBvp toxins and biofilm formation in AHPND causing Vibrio parahaemolyticus - Michael Eniola Ayenero; Ramya Kumar; Han-Ching Wang; Phuoc Thien Le; Yu-Hsuan Chen; Chu Fang Lo; Shin-Jen Lin; Hao-Ching Wang (Fish & Shellfish Immunology, 2025)

β–phase polymer-driven enhanced powder flowability and microstructure uniformity for stable and fast dry-processed electrode - Min Jang; Hyeongseok Shim; Sijeong Park; Hyeju Shin; Jeong-Rae Jo; Wooyoung Jin; Hyungyeon Cha; Jung Hoon Kim; Joong Tark Han; Gyujin Song; Sinho Choi (Chemical Engineering Journal, 2025)

Upcycling polycrystalline silicon from waste solar cells for thermally conductive epoxy composites: Anisotropic crystallite growth and tailored microstructure via heat treatment - Yoon Hye Han; Kyung Hoon Min; Hye In Kang; Yu Min Lim; Haolin Wang; Hyunseong Shin; Sang Eun Shim (Chemical Engineering Journal, 2025)

Case Study of Optimization of Pipeline Diameter in an Integrated Farm Pond–Pump–Pipeline System for Efficient Paddy Irrigation - Junyoung Lee; Sangjoon Bak; Hyungjin Shin; Dongjun Lee; Jeongho Han; Kyoung Jae Lim (Water Conservation Science and Engineering, 2025)

First Report of Scrippsiella irregularis Attaran-Fariman & Bolch (Dinophyceae) from Korean Coastal Waters - Minseok Jeong; Da Bin Choi; Zhun Li; Kyong Ha Han; Jinik Hwang; Hyeon Ho Shin (Ocean Science Journal, 2025)

Reducing electrical conductivity of nutrient solution to prevent rhizosphere salt accumulation and its impact on cherry tomato growth and fruit characteristics in hydroponics - Jeong Yeon Kim; Su Kyeong Shin; Jong Won Park; Han Na Kim; Govind D. Vyavahare; Jin Hee Park (Horticulture, Environment, and Biotechnology, 2025)

Integrating miRNAs with QTL for identification of milk and reproduction related traits in dairy cattle - Wonseok Shin; Seyoung Mun; Songmi Kim; Byung Sun Yu; Kornsorn Srikulnath; Kung Ahn; Kyudong Han (Genes & Genomics, 2025)

Evaluation of intermediate compounds in β-carboline alkaloids formation using model system including isotope labeled glycerol - Kyung-Jik Lim; Han-Seung Shin (Food Chemistry, 2025)

Association Between ABCG2 Polymorphism and Statin-Induced Adverse Events: A Meta-Analysis - Da Hoon Lee; Hae Ji Shin; Beom Yoon; Han Wool Kim; Hyeon Woo Jo; Hee Jung Kim; Woorim Kim (Cardiovascular Toxicology, 2025)

Living roots enhance the decomposition of dead roots rather than native organic matter in rice soils under elevated [CO2] and warming - Nuri Baek; Xuehua An; Seo-Woo Park; Eun-Seo Shin; Jiyu Lee; Han-Yong Kim; Woo-Jung Choi (Biology and Fertility of Soils, 2025)

Ship-hull mediated introduction risk of Colaconema formosanum: barnacle-associated dispersal and ecophysiological potential for coastal establishment - Ju-Hyoung Kim; Ye Rim Kim; Min Gui Jung; Eun Ju Kang; Kyoungsoon Shin; Bonggil Hyun; Jung-Hoon Kang; Seung Ho Baek; Il-Nam Kim; Jong Won Han; Jee Eun Lee; Hyung Woo Lee (Biological Invasions, 2025)

Impeller-driven scrubber system for enhanced nitric oxide capture using Fe(II)EDTA - Shin Han; Hyun-Woo Kim; Gwangtaek Lee; Sunghyeon Han; Jong-In Han (Journal of Environmental Chemical Engineering, 2025)

Reevaluating carbonization: The untapped potential of pristine ZIFs for lithium metal batteries - Jihyeon Kang; Ohhyun Kwon; Seungwoo Choi; Seyoung Choi; Seohyeon Jang; Hojong Eom; Junhyeop Shin; Jongkwon Park; Jae Hyun Kim; Myeong-Lok Seol; Jeong Woo Han; Soomin Park; et al. (Chemical Engineering Journal, 2025)

Ninety-day repeated oral toxicity and genetic toxicity studies of powderized Aurantii Fructus Immaturus - Soyoung An; Songyeon Kim; Si-Whan Song; Hye-Seon Heo; Changwook Park; Minseob Kim; Wooju Lee; Yujin Park; Jae-Ho Shin; Beom Seok Han; Wan-Seob Cho (Regulatory Toxicology and Pharmacology, 2025)

Triflumizole induces excessive reactive oxygen species, inhibits the GPR30/PI3K/AKT pathway, and triggers apoptosis and autophagy in GC-1 spermatogonia cells - Seul Gi Kim; Dong-Jin Yoon; Daniel Chavez Varias; Gi Jeong Ahn; Gil Un Han; Sung-Hwan Moon; Hee-Seok Lee; Seung Hee Shin; Buom-Yong Ryu (Pesticide Biochemistry and Physiology, 2025)

Growth enhancement of harmful dinoflagellate Prorocentrum cordatum by bacterial community shifts driven by dissolved organic matter derived from raphidophyte Heterosigma akashiwo - Royoung Park; Joo-Hwan Kim; Jin Ho Kim; Sae-Hee Kim; Hyeon Ho Shin; Myung-Soo Han; Bum Soo Park (Harmful Algae, 2025)

Surfactant-assisted colloidal size and charge control in perovskite solutions for high-performance and stable solar cells - Gyeong G. Jeon; Sang Eun Yoon; Jonghoon Han; Hye W. Chun; So Jeong Shin; Min Jun Choi; Sang Uk Park; Seo-Jin Ko; Shujuan Huang; Nochang Park; Jong H. Kim; Jincheol Kim (Chemical Engineering Journal, 2025)

Bile acid- and taurocholate-mediated virulence in AHPND-causing Vibrio parahaemolyticus is independent of the LuxO-OpaR quorum sensing cascade - Ramya Kumar; Shin-Jen Lin; Chien-Kang Huang; Shih-Shun Lin; Hao-Ching Wang; Fernand F. Fagutao; Han-Ching Wang (Aquaculture, 2025)

Changes in organic matter composition during poultry manure composting: A new perspective on compost maturity using DAX resin fractionation and spectroscopic analysis - Gyumin Kim; Woojin Chung; Jin Hur; Han Saem Lee; Hyun Sang Shin (Waste Management, 2025)

Prediction of garlic clove volume and mass using a depth camera and machine learning models - Jin-Ho Son; Hyung-Gyu Park; Yu-Jin Han; Seok-Ho Kang; Seung-Min Woo; Yu-Shin Ha (Postharvest Biology and Technology, 2025)

Optimization of synergistic microwave and zero–valent iron co–pretreatment for anaerobic digestion of waste activated sludge - Seung–han Ha; Seung Gu Shin; Johng–Hwa Ahn (Bioresource Technology, 2025)

In silico screening of epitopes as potential vaccine candidates against pathogenic Acinetobacter baumannii - Md. Minarul Islam; Kyudong Han; Ye-Ji Bang; Je Chul Lee; Woo Shik Shin; Man Hwan Oh (Genes & Genomics, 2025)

Assessment of ship hull-attached marine diatoms: species composition and reattachment - Jaeyeong Park; Buhari Lawan Muhammad; Taehee Kim; Quynh Thi Nhu Bui; Han-Sol Kim; Kyoungsoon Shin; Bonggil Hyun; Jung-Hoon Kang; Jang-Seu Ki (Marine Pollution Bulletin, 2025)

Sprayable Off-On DCP detection: Biocompatible carboxamide-based sensor with fluorescent signaling and colorimetric coagulation trigger - Moein Safarkhani; Fahimeh Taghavimandi; Yonghyeon Park; Amirhossein Ojaghi; Donghyeon Kim; Soobin Han; Hanseung Kim; Ali Mohammadi; Min Gyu Kim; Poojitha Yanamala; Reza Maleki; Sang Myeon Lee; et al. (Journal of Hazardous Materials, 2025)

Quercetin-loaded candelilla wax/sunflower oil oleogels: Structural, sensory, and storage properties, and application as fat replacer in emulsion-type sausage - Hyun Ju Lee; Jong Hyeon Han; Dong Hyun Keum; Vahinika Kothuri; Dong-Min Shin; Sung Gu Han (Food Chemistry, 2025)

Tailoring Cu3Nx clusters on TiO2 nanosheets to the sub-nanometric scale for enhancing NH3 photosynthesis - Hyun Sik Moon; Yu-Jeong Yang; Getasew Mulualem Zewdie; Geon Youn; Yi-An Chen; Yu-Peng Chang; Kai-Chi Hsiao; Ting-Han Lin; Yi-Dong Lin; Jun Kue Park; Jucheol Park; Yan-Gu Lin; et al. (Chemical Engineering Journal, 2025)

Disinfection of human coronavirus-229E on hospital cotton fabric via multi-cylinder dielectric barrier discharge plasma-generated reactive nitrogen species - Sekar Ashokkumar; Jun Sup Lim; Jinsung Choi; Shaik Abdul Munnaf; Ihn Han; Neha Kaushik; Nagendra Kumar Kaushik; Yung Oh Shin; Eun Ha Choi (Chemical Engineering Journal, 2025)

Blood Cells as a Cellular Biomarker for Mitochondrial Function in a Experimental Model of Acute Carbon Monoxide Poisoning with Treatment - Devesh Bungatavula; John C. Greenwood; Frances S. Shofer; Guthrie Buehler; Shih-Han Kao; Matthew Kelly; Samuel S. Shin; Johannes K. Ehinger; Todd J. Kilbaugh; David H. Jang (Journal of Medical Toxicology, 2025)
Introduction Carbon monoxide (CO) is a leading cause of environmental poisoning in the United States with substantial mortality and morbidity. The mechanism of CO poisoning is complex and includes hypoxia, inflammation, and mitochondrial dysfunction. Currently both biomarkers and therapies for CO poisoning are limited and require new approaches. Methods Rats (~ 300 g) were divided into four groups of ten rodents per group (exposure): Control (room air), CO-400 (400 ppm), CO-1000 (1000 ppm) and CO-2000 (2000 ppm). Rodents received the assigned exposure through a secured tracheotomy tube over 120 min followed by 30 min of re-oxygenation at room air for a total of 150 min. Five additional rodents in each group were administered a succinate prodrug (NV354) at the start of exposure for the duration of the experiment until the reoxygenation period as separate experiments. Cortical brain tissue and whole blood were obtained for mitochondrial respiration. Stored plasma and snap frozen tissue stored at -80 o C were used to obtain protein quantification with Western Blotting. Results All animals in the Sham, CO-400, and CO-1000 groups survived until the end of the exposure period; no animals in the CO-2000 groups survived the exposure and were counted as attrition. We observed a dose-dependent decrease in key respiratory states in both isolated brain mitochondria and peripheral blood mononuclear cells (PBMCs), and, PBMCs respiration more positively correlated with isolated brain mitochondria when compared to carboxyhemoglobin (COHb). There was no significant difference in mitochondrial respiratory states in animals treated with NV354 compared to the untreated group. Conclusions The primary findings from this study include: (1) A dose-dependent decrease with key respiration states with higher concentrations of CO; (2) PBMCs had a higher correlation to isolated brain mitochondria respiration when compared to COHb; and (3) there was no treatment effect with the use of NV354.

Heavy metal contamination in fish and human health risks from lakes of a mega inter-basin water diversion - Wenxia Fan; Wentong Xia; Lian-Shin Lin; Han Liu; Xiao Qu; Wei Xin; Lizhou Tang; Yushun Chen (Chemosphere, 2025)

Photosynthesis genes modulate cadmium tolerance in the freshwater alga Closterium acutum revealed by transcriptome analysis - Jeongmin Shin; Han-Sol Kim; Quynh Thi Nhu Bui; Taehee Kim; Jang-Seu Ki (Journal of Applied Phycology, 2025)

Leveraging large language models in pharmacometrics: evaluation of NONMEM output interpretation and simulation capabilities - Hwa Jun Cha; Kyuyeon Choe; Euibeom Shin; Murali Ramanathan; Sungpil Han (Journal of Pharmacokinetics and Pharmacodynamics, 2025)

Acute toxicity of antifouling agents CuSO4, ZnPT, and CuPT on marine diatoms Skeletonema costatum and Navicula sp. - Taesoo Kim; Huijeong Byeon; Yunji An; Vijay Rayamajhi; Jihyun Lee; Jong Dae Lee; Kwang Soo Lee; Chul-Hyun Kim; Juwon Oh; Jung Han Park; Hyun Woung Shin; Sang Mok Jung (Marine Environmental Research, 2025)

Unlocking design strategies for oxygen evolution reaction catalysts: Insights from a kinetic perspective via constrained ab initio molecular dynamics simulations - Dongyup Shin; Sang Soo Han (Chemical Engineering Journal, 2025)

Mechanisms of arsenic oxidation and immobilization by structural and surface iron-modified nontronite - Ji-Hyun Park; Dong Yun Shin; Dong-Hee Lim; Jin Young Kim; Young Heon Kim; Eun-Ji Bae; Young-Soo Han (Chemical Engineering Journal, 2025)

Improved method for estimating trophic position of the coastal blooming moon jellyfish aurelia coerulea: considering large carbon trophic discrimination factors and diet contributions - Heejoong Kim; Dokyun Kim; Bohyung Choi; Young-Ok Kim; Chang-Hoon Han; Jinho Chae; Eun-Ji Won; Kyung-Hoon Shin (Marine Biology, 2025)

Acid-activated bentonite for solid-phase nucleic acid extraction from various pathogenic samples - Eun Yeong Lee; Minju Lee; Myoung Gyu Kim; Chae Eun Bae; Sung-Han Kim; Yong Shin (Analytica Chimica Acta, 2025)

Carbon nanotube/metal organic framework hybrid scaffolds for scalable and self-structured OER catalyst coating: From rheology study to MEA fabrication - Suhyeon Lee; Yunseong Ji; Gisu Doo; MinJoong Kim; Jooyoung Shin; Chansol Kim; Man Ho Han; Woong Hee Lee; Jong Hyup Lee; Yeonji Kwak; Eunji Choi; Yonghwi Cho; et al. (Chemical Engineering Journal, 2025)

Enhanced flexibility of WO3-based flexible electrochromic devices for smart windows via ion beam treatment - Chang-Shin Park; Seunghoon Park; Hosung Cheon; Han-Ki Kim (Chemical Engineering Journal, 2025)

In-situ printing of an oxygen-generating tubular alginate hydrogel embedding Chlorella vulgaris - Hwarueon Lee; Sungchul Shin; Hyuntaek Han; Jinho Hyun (Bioresource Technology, 2025)

Atypical absorption response to the trans-thylakoid electric field in the acidothermophilic red algae Cyanidioschyzon merolae and Galdieria partita - Guan-Lin Wu; Shin-Ying Tzeng; Benjamin Bailleul; Julien Sellés; You-Yuan Zhang; Han-Yi Fu (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2025)

Multiple measures to mitigate methane emissions from organic rice fields: a review and future challenges - Nuri Baek; Se-In Lee; Husna Israt Pia; Seo-Woo Park; Eun-Seo Shin; Miwa M. Yashima; Han-Yong Kim; Hyun-Jin Park; Woo-Jung Choi (Journal of Soils and Sediments, 2025)

Enhancing indigenous plant growth in metal(loid) contaminated soil using biochar - Han Na Kim; Keum Chul Yang; Su Kyeong Shin; Yeong Ju Seok; Ju-Sung Cho; Hyo Kyung Jee; Jeong Yeon Kim; Jin Hee Park (Chemosphere, 2025)

Core-shell structured BN/SiO2 nanofiber membrane featuring with dual-effect thermal management and flame retardancy for extreme space thermal protection - Duo Pan; Ziyuan Han; Junting Lei; Yutao Niu; Hu Liu; Sunmi Shin; Chuntai Liu; Zhanhu Guo (Science Bulletin, 2025)

Neurotoxic effects of citronellol induced by the conversion of kynurenine to 3-hydroxykynurenine - Seong Soon Kim; Suhyun Kim; Yeonhwa Kim; Youngran Ha; Hyojin Lee; Hyunji Im; Jung Yoon Yang; Dae-Seop Shin; Kyu-Seok Hwang; Yuji Son; Sung Bum Park; Ki Young Kim; et al. (Journal of Hazardous Materials, 2025)

Performance of weighted genomic BLUP and Bayesian methods for Hanwoo carcass traits - Md Azizul Haque; Eun-Bi Jang; Han-Deul Lee; Dae-Hyun Shin; Ji-Hee Jang; Jong-Joo Kim (Tropical Animal Health and Production, 2025)

Enhancing toxicity prediction for natural products in herbal medicine and dietary supplements: Integrating (Q)STR models and in vitro assays - Hyun Kil Shin; Se-Myo Park; Mi-Sun Choi; Jung-Hwa Oh; Sang Kyum Kim; Seokjoo Yoon; Hae-Ryung Park; Hyoung-Yun Han (Toxicology and Applied Pharmacology, 2025)

Transparent and visible light-activated antimicrobial air filters from electrospun crystal violet-embedded polyacrylonitrile nanofibers - Seung Yeon Lee; Jae Hak Shin; In Ho Kim; Dong Yun Choi; Dong Uk Lee; Gi Byoung Hwang; Bangwoo Han; Sang Bok Kim; Dong-Keun Song; Inyong Park; Jae Hee Jung (Environmental Research, 2025)

Electrospun 1D Al-LLZO incorporated PVDF-HFP composite electrolyte with fast Li+ pathway derived from highway-traction effect for high performance lithium metal batteries - Joo-Young Han; Sunghoon Kim; Dae Ung Park; Dongwoo Kang; Ji-Hui Oh; Da-Eun Hyun; Dong-Won Lee; Hwiyun Im; Jong-Min Oh; Sang-Mo Koo; Jeonghyun Kim; Jong Ho Won; et al. (Chemical Engineering Journal, 2025)

Antimicrobial efficacy of carvacrol-loaded curdlan hydrogels for enhancing shelf-life in seafood packaging applications - Hong-Ting Victor Lin; Yi-Chi Yu; Shu-Han Yu; Yu-Chieh Chou; Hsuan-Ju Lin; Shella Permatasari Santoso; Shin-Ping Lin (International Journal of Food Microbiology, 2025)

Enhancement of skin longevity through TGF-β/Smad signaling pathway modulation by Rohu fish (Labeo rohita) collagen peptides in chronologically aged hairless mice - Hae Dun Kim; Yeok Boo Chang; Hyung Joo Suh; Sung Hee Han; Eun Yeong Jang; Eun Mi Sun; Hyung Shik Shin; Yejin Ahn (Food Bioscience, 2025)

Cytotoxicity-reducing and anti-inflammatory effects of a natural herb mixture extract - Jun-Ho Ahn; Sang-Hyun Shin; Se-Myo Park; Mi-Sun Choi; Soojin Kim; Jung-Hwa Oh; Seokjoo Yoon; Eun-Jung Park; Hyoung-Yun Han (Molecular & Cellular Toxicology, 2025)

Benefits of tidal admittance functions for refining GNSS-observed solar and lunisolar tidal constituents - Hao Wang; Na Wei; Min Li; Shin-Chan Han; Yunfei Xiang; Qile Zhao (GPS Solutions, 2025)

Analysis of key pathways and genes in nodal structure on rat skin surface using gene ontology and KEGG pathway - Joonyoung Shin; A. Yeong Park; Suk Ju; Hyorin Lee; Hyung Won Kang; Dongwoon Han; Sungchul Kim (Genes & Genomics, 2025)

Optimized antifouling γ-Al2O3/α-Al2O3 nanofiltration composite membrane for lignin recovery from wastewater - Xuelong Zhuang; Sung Woo Han; Min Chang Shin; Jae Yeon Hwang; Jung Hoon Park (Water Research, 2024)

Immobilization of erythrosine dye in polysiloxane to fabricate a cost-effective renewable antibiotic film through visible light-induced singlet oxygen generation - Nakyeong Lee; Byeonghwak Bae; Won-Sik Han; Il-Kwon Bae; Jun-Yong Shin; Kang-Kyun Wang; Jae-Min Oh; Jin Kuen Park (Journal of Cleaner Production, 2024)

Validation of analytical methods for newly regulated veterinary drug residues in livestock and fishery products with maximum residue limits in Republic of Korea - Dahae Park; Sang Beom Han; Ho-Chul Shin; Yong Seok Choi; Yu Ra Kim; Ji Young Kim; Gui-Hyun Jang; Miok Eom (Food Chemistry, 2024)

Development of a simultaneous analytical method for the dietary exposure determination of β-Carboline alkaloids in foods - Yoeseph Cho; Woo Yeon Jeong; Sungmin Hwang; Sunhwan Na; Hana Park; Soohyun Heo; Saeyeon Park; Kyung-Jik Lim; Han-Seung Shin; Junghyun Son (Food Chemistry, 2024)

Dynamics of Carbon Export and Lower Trophic Ecosystems: A Comparative Model Study in the Yellow Sea and Dokdo Waters - Young Shin Kwon; Hyoun-Woo Kang; Dong Han Choi; Ok Hee Seo (Ocean Science Journal, 2024)

Comprehensive analysis of somatic mutations and structural variations in domestic pig - Seong Gyu Kwon; Geon Hue Bae; Joo Hee Hong; Jeong-Woo Choi; June Hyug Choi; Nam Seop Lim; CheolMin Jeon; Nanda Maya Mali; Mee Sook Jun; JaeEun Shin; JinSoo Kim; Eun-Seok Cho; et al. (Mammalian Genome, 2024)

Jatrophihabitans cynanchi sp. nov., isolated from rhizosphere soil of Cynanchum wilfordii - Min Kuk Suh; Ji-Sun Kim; Mi Kyung Eom; Han Sol Kim; Hyo Eun Do; Yong Kook Shin; Jung- Sook Lee (Antonie van Leeuwenhoek, 2024)

A novel low-cost and simple fabrication technique for a paper-based analytical device using super glue - Hyo-eun Kang; The Huy Bui; Won Han; Yong-Ill Lee; Joong Ho Shin (Analytica Chimica Acta, 2024)

Comparison of drug-induced liver injury risk between propylthiouracil and methimazole: A quantitative systems toxicology approach - Qingfeng He; Min Li; Peiying Ji; Aole Zheng; Li Yao; Xiao Zhu; Jae-Gook Shin; Volker M. Lauschke; Bing Han; Xiaoqiang Xiang (Toxicology and Applied Pharmacology, 2024)

Mechanistic insights into selenite and selenate immobilization using brucite-rich magnesium precipitate derived from seawater electrochlorination facility - Han Gyeol Jeon; Seonggyu Choi; Jin-Seok Kim; Kyung-Hee Lee; Jaegwan Shin; Kangmin Chon; Kyoung-Woong Kim; Sang-Ho Lee (Journal of Environmental Chemical Engineering, 2024)

Prediction of food materials for the management of respiratory symptoms targeting PDE4B and NMDAR via machine learning approach - Jihyeon Jung; Seo Hyun Shin; Jong Hun Kim; Jung Han Yoon Park; Ki Won Lee (Food Bioscience, 2024)

Insights into water mass change in the Yangtze River Basin from the spectral integration of GNSS and GRACE observations - Miao Tang; Linguo Yuan; Xinghai Yang; Zhongshan Jiang; Shin-Chan Han; Wei You (Earth and Planetary Science Letters, 2024)

FeNiCo@lyocell-based carbon cloth cathode for enhanced seawater electrolysis with bipolar membrane - Jung Jae Lee; Hyunji Eom; Hong Gun Kim; Namjo Jeong; Young Sun Mok; Hye Kyoung Shin; Ji-Hyung Han (Chemical Engineering Journal, 2024)

Chemical optimization and derivatization of micrococcin p2 to target multiple bacterial infections: new antibiotics from thiopeptides - Jiyun Park; Dahyun Kim; Young-Jin Son; Marco A. Ciufolini; Shyaka Clovis; Minwoo Han; Lee-Han Kim; Sung Jae Shin; Hee-Jong Hwang (World Journal of Microbiology and Biotechnology, 2024)

Sub-minute carbonization of polymer/carbon nanotube films by microwave induction heating for ultrafast preparation of hard carbon anodes for sodium-ion batteries - Gyeongbeom Ryoo; Jiwon Shin; Byeong Guk Kim; Do Geun Lee; Joong Tark Han; Byeongho Park; Youngseok Oh; Seung Yol Jeong; Se-Hee Lee; Dong Yun Lee; Daeho Kim; Jong Hwan Park (Chemical Engineering Journal, 2024)

Atomically dispersed Rh catalysts formed on defective CeO2 surfaces with hydroformylation activity - Hojeong Lee; Dongjae Shin; Daewon Oh; Beomgyun Jeong; Kwang Young Kim; Changhun Hur; Jeong Woo Han; Kwangjin An (Chemical Engineering Journal, 2024)

Rational design of polymer-based insulating scaffolds for high-capacity lithium metal batteries - Jinhyeon Jo; Subin Kim; JunHwa Kwon; Ki-Yeop Cho; Hayong Song; Jaewook Shin; Seung Jong Lee; Wonkeun Kim; Kyoung Han Ryu; KwangSup Eom (Chemical Engineering Journal, 2024)

Finite element analysis-based blast and seismic performance evaluation for RC frame with retrofitted ENTA damper systems - Quoc Bao To; Jiuk Shin; Jaeyoung Kim; Sang Whan Han; Kihak Lee (Engineering Structures, 2024)

Valorization of battery manufacturing wastewater: Recovery of high-value metal ions through reaction-enhanced membrane cascade - Jeong Han Shin; Seung Hwan Kim; Cheol Hun Yoo; Ho Jun Lee; Bao Tran Duy Nguyen; Go Gi Lee; Jeong F. Kim; Jong Suk Lee (Chemical Engineering Journal, 2024)

Nitrate formation mechanisms causing high concentration of PM2.5 in a residential city with low anthropogenic emissions during cold season - Ji-Won Jeon; Sung-Won Park; Young-Ji Han; Taehyoung Lee; Seung-Ha Lee; Jung-Min Park; Myung-Soo Yoo; Hye-Jung Shin; Philip K. Hopke (Environmental Pollution, 2024)

Luxury application of biochar does not enhance rice yield and methane mitigation: a review and data analysis - Husna Israt Pia; Nuri Baek; Seo-Woo Park; Eun-Seo Shin; Sun-Il Lee; Han-Yong Kim; Shuirong Tang; Weiguo Cheng; Jin-Hyeob Kwak; Hyun-Jin Park; Woo-Jung Choi (Journal of Soils and Sediments, 2024)
Purpose It is unclear whether a higher biochar (BC) application rate enhances rice ( Oryza sativa L.) yield and reduces CH 4 emissions. This study investigated changes in rice yield and CH 4 emissions with varying BC application rates. Methods Data on rice yield and CH 4 emission from paddies amended with or without BC were collected from the literature, and the biochar effects were analyzed using the data set. Results Across the biochar application rate from 2 to 48 t ha -1 , the rice yield increased (by 10.8%) while the area-scaled (by 14.4%) and yield-scaled CH 4 emission (by 22.2%) decreased. However, the correlation of BC application rates with rice yield and CH 4 mitigation was not significant, implying that a higher BC application rate did not enhance rice yield and CH 4 reduction. Interestingly, for a data set showing increased rice yield and decreased CH 4 emission by BC, the magnitude of change in the rice yield and CH 4 mitigation per unit weight of BC (1 t ha -1 ) decreased with an increase in the BC application rate. These results suggest that BC effects on rice yield and CH 4 mitigation are not additive, probably because of the decreases in the inherent capacity of unit weight of BC to enhance rice yield and reduce CH 4 emission, which might be caused by the adverse effects of toxic compounds contained in BC, losses of BC, and a higher degree of nutrient immobilization by BC. Conclusions Annual BC application at a low rate (e.g., 2 t ha -1 ) rather than a luxury application may be an effective and economical strategy for long-term rice yield enhancement and CH 4 mitigation using BC.

Transcriptome sequencing of the endangered land snail Karaftohelix adamsi from the Island Ulleung: De novo assembly, annotation, valuation of fitness genes and SSR markers - Jie Eun Park; Bharat Bhusan Patnaik; Min Kyu Sang; Dae Kwon Song; Jun Yang Jeong; Chan Eui Hong; Yong Tae Kim; Hyeon Jun Shin; Liu Ziwei; Hongray Howrelia Patnaik; Hee Ju Hwang; So Young Park; et al. (Genes & Genomics, 2024)

In silico identification and expression analysis of superoxide dismutases in Tenebrio molitor - Ho Am Jang; Hyeonjun Shin; Seo Jin Lee; Sung Min Ku; Jae Hui Kim; Dong Woo Kang; So Yeon Choi; Sang Mok Jung; Hyun Woung Shin; Yong Seok Lee; Yeon Soo Han; Yong Hun Jo (Genes & Genomics, 2024)

Anti-obesogenic effects of plant natural products: A focus on Korean traditional foods - Gitishree Das; Luis Alfonso Jiménez Ortega; Sandra Gonçalves; J. Basilio Heredia; Maria de Lourdes Gomes Pereira; Anabela Romano; Han-Seung Shin; Jayanta Kumar Patra (Trends in Food Science & Technology, 2024)

Performance and techno-economic evaluation of a high-efficiency electrospray cyclone - Jun Su Park; Dae-Gyun Lee; Kang-San Lee; Jin-Han Kim; Jung Hoon Yoo; Hang Joo Shin; Young-Chan Choi; Young-joo Lee; YoungMin Woo; Meehye Lee; Jong Won Choi (Journal of Environmental Chemical Engineering, 2024)

Antiperiodontitis impact of extract from edible herb Aster glehni and its bioactive compound, 3,5-dicaffeolyquinic acid - Gweon Ah Kang; Sung Ran Yoon; Yong Jin Jeong; Min-sook Kang; Haeng-ran Kim; Han-Seung Shin; Seok-Seong Kang (Food Bioscience, 2024)

Corrigendum to “Physicochemical and in-vitro release characteristics of vitamin C-loaded antioxidant orally disintegrating films with different catechin levels” [Food Bioscience 53 (2023) /102733] - Hejeong Shin; Jin-Hee Chang; Jung-Ah Han (Food Bioscience, 2024)

Modulations of ocean-atmosphere interactions on squid abundance over Southwest Atlantic - Chia-Ying Ko; Yu-Chi Lee; Yi-Chi Wang; Huang-Hsiung Hsu; Chun Hoe Chow; Ruei-Gu Chen; Tsung-Han Liu; Chih-Shin Chen; Tai-Sheng Chiu; Don-Hsieh Chiang; Ren-Fen Wu; Wan-Ling Tseng (Environmental Research, 2024)

Promoter regions of sxtA and sxtG reveal relationship between saxitoxin biosynthesis and photosynthesis in toxic Alexandrium catenella - Han-Sol Kim; Quynh Thi Nhu Bui; Jeongmin Shin; Hui Wang; Jang-Seu Ki (Journal of Applied Phycology, 2024)

Removal efficiency of antibiotic residues, antibiotic resistant bacteria, and genes across parallel secondary settling tank and membrane bioreactor treatment trains in a water reclamation plant - Hongjie Chen; Charmaine Ng; Ngoc Han Tran; Laurence Haller; Shin Giek Goh; Francis Rathinam Charles; Zhixin Wu; Jit Xin Lim; Karina Yew-Hoong Gin (Science of The Total Environment, 2024)

Benzyl-methylbenzyl-benzene: Improving hydrogen storage and release performance of dibenzyltoluene based liquid organic hydrogen carrier - Kwanyong Jeong; Hyunwoo Yook; So Hyeon Lee; Hwa Jin Han; Yunkyeong Jung; Seulgi Han; So Yeon Shin; Myungho Choi; Sunil Kwon; Jin Hee Lee; Sang-Joon Kim; Soo Min Kim; et al. (Chemical Engineering Journal, 2024)

Multi-functional energy conversion by strongly coupled Ag3PO4/ZIF-67 heterostructures - Harshavardhan Mohan; Sethumathavan Vadivel; Suhwan Yoo; Ga Hyeon Ha; Gitae Kim; Hye Rin Lee; Han-Kyu Choi; Taeho Shin (Journal of Environmental Chemical Engineering, 2024)

Bioactive compounds obtained via subcritical water hydrolysis of Ecklonia stolonifera: Characterization and potential application - Ye-Seul Park; Vikash Chandra Roy; Jin-Seok Park; Ji-Min Han; Yu-Na Shin; Ye-Ryeon Shin; Sin-Won Park; Byung-Soo Chun (Journal of Applied Phycology, 2024)

Genetic diversity and population relationships in wild Korean black raspberry (Rubus coreanus Miq.) based on microsatellite markers: establishing a fruit tree breeding strategy - Sung-Kyung Han; Hanna Shin; Jei-Wan Lee; Kyung-Nak Hong; Ji-Young Ahn (Horticulture, Environment, and Biotechnology, 2024)

Stretchable and biodegradable composite films for disposable, antibacterial, radiative cooling system - Won Bae Han; Heeseok Kang; Se-Yeon Heo; Yelynn Ryu; Gyuil Kim; Gwan-Jin Ko; Jeong-Woong Shin; Tae-Min Jang; Sungkeun Han; Jun Hyeon Lim; Chan-Hwi Eom; Young Min Song; et al. (Chemical Engineering Journal, 2024)

Isopropanol production using engineered Corynebacterium glutamicum from waste rice straw biomass - Xiaoyu Shi; Joonhee Chang; Minhye Kim; Myeong-Eun Lee; Ha-Young Shin; Sung Ok Han (Bioresource Technology, 2024)

Long-term changes in temperature, specific humidity, and precipitation in Bangladesh revealed by ERA5 data - Abeda Tabassum; Kyeongjoo Park; Jihoon Shin; Han-Gyul Jin; Jong-Jin Baik (Theoretical and Applied Climatology, 2024)

Development of polymorphic simple sequence repeat markers in Agastache rugosa and their application in genetic evaluation and cross-taxon transferability of Agastache species - Hye Ran Shin; Ick Hyun Jo; Raveendar Sebastin; Jinsu Gil; Gi Yeong Kim; Suyun Moon; Hyun-Seung Park; Sewon Oh; Jong Won Han; Kyung Ho Ma; Yi Lee; Daeil Kim; et al. (Journal of Applied Research on Medicinal and Aromatic Plants, 2024)

Diisobutyl phthalate (DiBP)-induced male germ cell toxicity and its alleviation approach - Seok-Man Kim; Yong-Hee Kim; Gil Un Han; Seul Gi Kim; Dong Ha Bhang; Byung-Gak Kim; Sung-Hwan Moon; Seung Hee Shin; Buom-Yong Ryu (Food and Chemical Toxicology, 2024)

Clinical outcomes and immunological features of COVID-19 patients receiving B-cell depletion therapy during the Omicron era - Chan Mi Lee; Minji Kim; Seong-wook Park; Chang Kyung Kang; Pyoeng Gyun Choe; Nam Joong Kim; Hyeon Jae Jo; Hyun Mu Shin; Chang-Han Lee; Hang-Rae Kim; Wan Beom Park; Myoung-don Oh (Infectious Diseases, 2024)

Economic benefits of urban streetscapes: Analyzing the interrelationships between visual street environments and single-family property values in Seoul, Korea - Ayoung Woo; Jaewon Han; Hyungsup Shin; Sugie Lee (Applied Geography, 2024)

Development of Biological Risk Assessment Protocols for Evaluating the Risks of In-Water Cleaning of Hull-Fouling Organisms - Bonggil Hyun; Pung-Guk Jang; Min-Chul Jang; Jung-Hoon Kang; Ju-Hyoung Kim; Jang-Seu Ki; Dong Han Choi; Ok Hwan Yu; Jin-Young Seo; Woo-Jin Lee; Kyoungsoon Shin (Journal of Marine Science and Engineering, 2024)
Herein, we evaluate the scientific basis for managing hull fouling of ships entering Korean ports, diagnose biological risks that may occur when in-water cleaning (IWC) systems remove hull fouling, and present a protocol for evaluating these risks (the Korean Infection Modes and Effects Analysis; K-IMEA). Protocol development included the selection of core elements and scenario design for IWC and the evaluation of regrowth experiments. The K-IMEA index was designed by considering the inoculation pathway of attaching organisms in all processes to ships that enter a port for in-water cleaning. A number of risk indices were defined: R1—Introduction/Establishment of alien species before in-water cleaning; R2—Establishment of alien species escaped during in-water cleaning; R3—Introduction/Establishment of alien species after in-water cleaning; and R4—Establishment of alien species in effluent water. K-IMEA regrowth experiments (R2 and R4) using the in-water cleaning effluent showed that the attachment and regrowth of prokaryotes, microalgae, and macroalgae were successfully detected. In particular, prokaryotes were observed in samples filtered through a 5 μm mesh of the in-water cleaning effluent, even at a low fouling rating (Levels 1–2). These experiments suggest a necessity to consider a secondary treatment method in addition to the primary filtration method for the treatment of in-water cleaning effluents.

Isolation of a quorum quenching bacterium effective to various acyl-homoserine lactones: Its quorum quenching mechanism and application to a membrane bioreactor - Soyoung Ham; Hwa-Soo Ryoo; Yongsun Jang; Sang-Hoon Lee; Ji-Yoon Lee; Han-Shin Kim; Jeong-Hoon Lee; Hee-Deung Park (Chemosphere, 2024)

Effect of wastewater collection and concentration methods on assessment of viral diversity - Yabing Li; Brijen Miyani; Kevin L. Childs; Shin-Han Shiu; Irene Xagoraraki (Science of The Total Environment, 2024)

Evaluation of the impact of transition from porous to fractured rock media on 3D field-scale DNAPLs contamination - Taehoon Kim; Weon Shik Han; Seonkyoo Yoon; Peter K. Kang; Jehyun Shin; Myung Jin Nam (Journal of Hazardous Materials, 2024)

Effects of water direct injection on a combustion phase and performance of six-stroke gasoline homogeneous charge compression ignition engine - Woo Jae Shin; Han Ho Song (Fuel, 2024)

Improved estimation of ocean tide loading displacements using multi-GNSS kinematic and static precise point positioning - Hao Wang; Min Li; Na Wei; Shin-Chan Han; Qile Zhao (GPS Solutions, 2024)

Novel rearrangements in the mitochondrial genomes of the Ceramiales (Rhodophyta) and evolutionary implications - Min Ho Seo; Shin Chan Kang; Kyeong Mi Kim; Min Seok Kwak; Jihoon Jo; Han-Gu Choi; Ga Hun Boo; Hwan Su Yoon (Algae, 2023)
The Ceramiales is the most diverse and species-rich group (2,669 spp.) of red algae, and it is widely distributed from tropical to polar oceans. Mitochondrial genomes (mitogenomes) and other genes have contributed to our knowledge regarding the classification and phylogeny of this diverse red algal group; however, the mitogenome architecture remains understudied. Here, we compared 42 mitogenomes, including 19 newly generated in this study, to expand our knowledge. The number of genes in mitogenome varied from 43 to 68 due to gene duplication. The mitogenome architecture was also variable, categorized into four types (A–D): type A = ancestral type with a basic composition; type B = those with inverse transpositions; type C = those with inverted duplications; and type D = those with both inversion and duplication. T﻿he palindromic and inverted repeats were consistently found in flanking regions of the rearrangement, especially near the cob and nad6 genes. The three rearranged mitogenome architectures (types B, C, D) are the first report of these in red algae. Phylogenetic analyses of 23 protein-coding genes supported the current familial classification of the Ceramiales, implying that the diversity of mitogenome architecture preceded the phylogenetic relationships. Our study suggests that palindromic and inverted repeats may drive mitogenome architectural variation.

Emission characteristics of naphthalene from ship exhausts under global sulfur cap - Chin-Ko Yeh; Fu-Ming Tzu; Po-Yang Chen; Hsueh-Chen Shen; Chung-Shin Yuan; Chitsan Lin; Han-Pin Pu; Huu Hao Ngo; Xuan-Thanh Bui (Science of The Total Environment, 2023)

Investigating the different transformations of tetracycline using birnessite under different reaction conditions and various humic acids - Hang Vo-Minh Nguyen; Doo-Hee Lee; Han-Saem Lee; Hyun-Sang Shin (Environmental Pollution, 2023)

Estimation of GPS-observed ocean tide loading displacements with an improved harmonic analysis in the northwest European shelf - Hao Wang; Na Wei; Min Li; Shin-Chan Han; Rongxin Fang; Qile Zhao (Journal of Geodesy, 2023)

Holocene relative sea-level changes on the southern east coast of the Yellow Sea - Dong-Yoon Yang; Min Han; Hyun Ho Yoon; Jin Cheul Kim; Eunseo Choi; Won-Jeong Shin; Jong-Yeon Kim; Arum Jung; Chanhyeok Park; Chang-Pyo Jun (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Comparative life cycle greenhouse gas analysis of clean hydrogen pathways: Assessing domestic production and overseas import in South Korea - Woo Jae Shin; Yeim Lee; Yejin Yu; Minhyuck Ko; Chonghoh Lee; Han Ho Song (Journal of Cleaner Production, 2023)

Bacterial community structure, predicted metabolic activities, and formation of volatile compounds attributed to Malaysian fish sauce flavour - Shanti Dwita Lestari; Anis Shobirin Meor Hussin; Shuhaimi Mustafa; Yun Shin Sew; Han Ming Gan; Amalia Mohd Hashim; Norhayati Hussain (Food Chemistry, 2023)

Butylparaben promotes phosphatidylserine exposure and procoagulant activity of human red blood cells via increase of intracellular calcium levels - Yeonju Ko; Eun-Hye Kim; Donghyun Kim; Sungbin Choi; Junkyung Gil; Han Jin Park; Yusun Shin; Wondong Kim; Ok-Nam Bae (Food and Chemical Toxicology, 2023)

Stretchable and biodegradable triboelectric nanogenerator based on elastomeric nanocomposites - Heeseok Kang; Won Bae Han; Seung Min Yang; Gwan-Jin Ko; Yelynn Ryu; Joong Hoon Lee; Jeong-Woong Shin; Tae-Min Jang; Kaveti Rajaram; Sungkeun Han; Dong-Je Kim; Jun Hyeon Lim; et al. (Chemical Engineering Journal, 2023)

Effective bioconversion of fungal-spoiled starchy food waste into fermentable sugars using fungi-degrading, artificial amylosomes - Myeong-Eun Lee; Ha-Young Shin; Nisha Bhardwaj; Byeong-Hyeon Cho; Dong-Hyeok Hwang; Wu-Young Jeong; Sung Ok Han (Bioresource Technology, 2023)

Green chemical and hybrid enzymatic pretreatments for lignocellulosic biorefineries: Mechanism and challenges - Rijuta Ganesh Saratale; Vinoth Kumar Ponnusamy; Grzegorz Piechota; Bartłomiej Igliński; S. Shobana; Jeong-Hoon Park; Ganesh Dattatraya Saratale; Han Seung Shin; J. Rajesh Banu; Vinod Kumar; Gopalakrishnan Kumar (Bioresource Technology, 2023)

Distribution of nephrons in the head kidney of three species of Sebastes (Teleostei: Scorpaenidae) - Han Young Oh; So Ryung Shin; Jung Jun Park; Hyeon Jin Kim; Jung Sick Lee (Journal of Fish Biology, 2023)
Nephrons are generally not distributed in the head kidney of teleost. Nonetheless, in this study, the nephron structure was identified in the head kidney of three species of Sebastes ( Sebastes inermis , Sebastes schlegelii and Sebastes thompsoni ). The kidney is Y shaped, with the development in the head kidney. The nephron structure was confirmed in the head kidney and body kidney. In addition, the nephron consisted of renal corpuscles and tubules, and the renal corpuscle consisted of the Bowman's capsule and glomerulus. Histologically, previous studies reported that the nephron structure is similar to that of other marine teleost. The renal tubule is a simple columnar epithelial layer with microvilli and cilia on the free surface, which is observed as a brush border. The Rrk (relative area ratio of kidney to body surface) was 5.14%, 7.58% and 5.17% in S. inermis , S. schlegelii and S. thompsoni , respectively. The Gar (glomerular area ratio of the head kidney) was higher in the central area than in the peripheral area, and species, which showed significant difference ( P S. thompsoni (1.60%) > S. schlegelii (0.90%) > S. inermis (0.66%).

Corrigendum to “Physicochemical and in-vitro release characteristics of vitamin C-loaded antioxidant orally disintegrating films with different catechin levels” [Food Biosci. 53 (2023) 102733] - Hye-Jung Shin; Jin-Hee Chang; Jung-Ah Han (Food Bioscience, 2023)

Repercussion of extracellular polymeric removal by low-temperature calcium peroxide pretreatment on bacterial fragmentation for enhancing biohydrogen production - Do-Hyung Kim; Han-Shin Kim; Baek-Gyu Im; Jeong-Hoon Park (Bioresource Technology, 2023)

Sodium hydroxide-induced Weissella kimchii ghosts (WKGs) as immunostimulant - Young-Min Kim; Kwang-Su Lee; Won-Mun Kim; Min Kim; Han-Oh Park; Chang Won Choi; Joong-Soo Han; Shin-Young Park; Ki-Sung Lee (Molecular & Cellular Toxicology, 2023)

Cell-Free DNA as a Biomarker in a Rodent Model of Chlorpyrifos Poisoning Causing Mitochondrial Dysfunction - Shih-Han Kao; Frances S. Shofer; John C. Greenwood; Oladunni Alomaja; Abhay Ranganathan; Sarah Piel; Clementina Mesaros; Samuel S. Shin; Johannes K. Ehinger; Todd J. Kilbaugh; David H. Jang (Journal of Medical Toxicology, 2023)

Post-stroke movement disorders disappearance: a report of disappearance of tardive dyskinesia after stroke and a literature review - Min Seung Kim; InJa Shin; Don Gueu Park; Jung han Yoon (Acta Neurologica Belgica, 2023)

Shear Force and Bending Moment Tuning Algorithm of Shuttle Tanker Model for Global Structural Analysis - Chaeog Lim; Ik-seung Han; Ju-Young Kang; Im-jun Ban; Byungkeun Lee; Jun Soo Park; Sung-chul Shin (Journal of Marine Science and Engineering, 2023)
Global ship analysis is conducted using a finite element model (FE model) for ship design and construction, which involves structural, motion, and vibration analyses. It is crucial to examine the structural safety of the hull and motion response. In the ship FE model used in global ship analysis, weight distribution is employed to adjust the light weight and center of gravity (COG), which are required to perform the analysis. Further, the FE model needs to satisfy the required longitudinal shear force (SF) and bending moment (BM) under the loading conditions of the ship. Moreover, the SF and BM in the ship Trim and Stability data are utilized to perform shear force tuning (SFT) and bending moment tuning (BMT) for the ship FE model. This ensures the ship model exhibits curves of the SF and BM that coincide with those of the ship. The SFT and BMT for the ship FE model are time-consuming and costly. Thus, to address these limitations, we propose an effective and accurate algorithm and program for SFT and BMT. Accordingly, we developed a C#-based algorithm to tune the weight, SF, BM, and COG of the ship FE model to the required target value. Finally, the accuracy of the newly developed algorithm was analyzed and compared by applying it to the shuttle tanker FE model under the ballast and full load conditions. Accuracy was within tolerance in both loading conditions. The average errors of SF and BM were smaller in the ballast condition than in the full load condition, and the errors were smaller at the bow than at the stern.

The effects of environmental Microplastic on wharf roach (Ligia exotica): A Multi-Omics approach - Youmi Choi; Dongju Shin; Chang Pyo Hong; Dong-Min Shin; Sung-Hee Cho; Seong Soon Kim; Myung Ae Bae; Sang Hee Hong; Mi Jang; Youna Cho; Gi Myung Han; Won Joon Shim; et al. (Chemosphere, 2023)

Exaptation of I4760M mutation in ryanodine receptor of Spodoptera exigua (Lepidoptera: Noctuidae): Lessons from museum and field samples - Changhee Han; Md-Mafizur Rahman; Jiyeong Shin; Ju Hyeon Kim; Si Hyeock Lee; Min Kwon; Alicia E. Timm; Srinivasan Ramasamy; Youngsu Lee; Sera Kang; Suhyeong Park; Juil Kim (Pesticide Biochemistry and Physiology, 2023)

Investigation of the fall armyworm (Spodoptera frugiperda) gut microbiome and entomopathogenic fungus-induced pathobiome - Yao-Chia Liu; Tzu-Han Chen; Yu-Feng Huang; Chang-Lin Chen; Yu-Shin Nai (Journal of Invertebrate Pathology, 2023)

A review of the endangered mollusks transcriptome under the threatened species initiative of Korea - Hongray Howrelia Patnaik; Min Kyu Sang; Jie Eun Park; Dae Kwon Song; Jun Yang Jeong; Chan Eui Hong; Yong Tae Kim; Hyeon Jun Shin; Liu Ziwei; Hee Ju Hwang; So Young Park; Se Won Kang; et al. (Genes & Genomics, 2023)

Comparison of genetic variation between primary colorectal cancer and metastatic peritoneal cancer - Wonseok Shin; Jeongseok Yun; Kyudong Han; Dong-Guk Park (Genes & Genomics, 2023)

Spawning characteristics of blue sprat (Spratelloides gracilis) in the waters of Penghu, central Taiwan Strait - Li Chi Cheng; Yang Chi Lan; Kuo Wei Lan; Jinn Shing Weng; Yu Kai Chen; Sheng Tai Hsiao; Yi Sui Wu; Jia Shin He; Hsing Han Huang; Yu Cih Huang; Hung An Cheng (Frontiers in Marine Science, 2023)
Blue sprat ( Spratelloides gracilis ) is an economically valuable species that inhabits the central Taiwan Strait. However, despite the implementation of a local management scheme involving a closed season between 1 May and 1 June, the annual catch has rapidly decreased over the decades. Thus, the efficacy of the implemented regulations must be investigated. This study sought to clarify the reproductive biology, spawning ground, and behavior of this species in the waters of Penghu. In total, 6,549 specimens were collected between March 2021 and September 2022. Considering gonadosomatic index, group maturity, and oocyte diameter, we found that the spawning season (March–September) peaked in April; new cohorts were distinctly recruited after the spawning peak. The distribution of the spawning ground (latitude, 23°41′N to 23°43′N; longitude, 119°32′E to 119°39′E) was determined by considering the fishing area of mature females and DNA analysis of adhered eggs. We further noted shoals of fish darting in the bottom water without clear schooling movement, females’ abdomen frequently contacting substrata for eggs able to attach on during oviposition, and males releasing sperms making water milky white; these indicate that S. gracilis exhibits promiscuous spawning behavior. Our findings may facilitate the management and conservation of S. gracilis in this region.

Sericin mediated gold/silver bimetallic nanoparticles and exploration of its multi-therapeutic efficiency and photocatalytic degradation potential - Gitishree Das; SuJin Seo; In-Jun Yang; Ly Thi Huong Nguyen; Han-Seung Shin; Jayanta Kumar Patra (Environmental Research, 2023)

Bloom development of toxic dinoflagellate Alexandrium catenella (Group I) in Jinhae-Masan Bay, Korea: Germination strategy of resting cysts in relation to temperature and salinity - Hyeon Ho Shin; Moon Ho Son; Bum Soo Park; Kyung Ha Han; Joo Yeon Youn; Kyeong Yoon Kwak; Ji Hoon Lee; A-Young Shin; Eunjung Byun; Yeong Du Yoo; Min Ho Seo; Kyungsoon Shin; et al. (Marine Pollution Bulletin, 2023)

Identification of the cause of the difference among TOC quantitative methods according to the water sample characteristics - Joo-Won Kim; Han-Saem Lee; Hye-Bin Lim; Hyun-Sang Shin (Science of The Total Environment, 2023)

Physicochemical and in-vitro release characteristics of vitamin C-loaded antioxidant orally disintegrating films with different catechin levels - Hye-Jung Shin; Jin-Hee Chang; Jung-Ah Han (Food Bioscience, 2023)

Nanoparticle-Based Chimeric Antigen Receptor Therapy for Cancer Immunotherapy - Seungyong Shin; Pyunghwajun Lee; Jieun Han; Se-Na Kim; Jaesung Lim; Dae-Hwan Park; Taejong Paik; Junhong Min; Chun Gwon Park; Wooram Park (Tissue Engineering and Regenerative Medicine, 2023)

Analysis of volatile compounds of several rice varieties according to endosperm type using an electronic nose - Chae-Min Han; Jong-Hee Shin; Sang-Kuk Kim; Jung-Gi Ryu (Journal of Crop Science and Biotechnology, 2023)

Evaluation of a mixture of short-chain and medium-chain fatty acid glycerides as a dietary supplement in diets for Pacific white shrimp (Litopenaeus vannamei) - Jaebeom Shin; Julie Feyaerts; Mirasha Hasanthi; Chorong Lee; Danbi Shin; Yeonji Lee; Jongho Lim; Han-Se Kim; Kyeong-Jun Lee (Aquaculture International, 2023)

Systematic tracing of nitrate sources in a complex river catchment: An integrated approach using stable isotopes and hydrological models - Seung-Hee Kim; Dong-Hun Lee; Min-Seob Kim; Han-Pil Rhee; Jin Hur; Kyung-Hoon Shin (Water Research, 2023)

Inhibiting bacterial biofilm formation by stimulating c-di-GMP regulation using citrus peel extract from Jeju Island - Han-Shin Kim; So-Young Ham; Hwa-Soo Ryoo; Do-Hyung Kim; Eun-Tae Yun; Hee-Deung Park; Jeong-Hoon Park (Science of The Total Environment, 2023)

Improved natural food colorant production in the filamentous fungus Monascus ruber using CRISPR-based engineering - Hye Ree Yoon; Suk Han; Seung Chul Shin; Su Cheong Yeom; Hyo Jin Kim (Food Research International, 2023)

Modified viologen-assisted reversible bromine capture and release in flowless zinc–bromine batteries - Seung Hee Han; Seoyoung Kim; Hyeong Yong Lim; Sewon Park; Kyungjae Shin; Seungwon Kim; Hee-Tak Kim; Sang Kyu Kwak; Changduk Yang; Nam-Soon Choi (Chemical Engineering Journal, 2023)

Multipurpose advanced split T7 promoter-based transcription amplification for ultrasensitive molecular diagnostics - Jiye Shin; Taehwi Yoon; Daehan Nam; Doyeon Kim; Seokjoon Kim; Byung Seok Cha; Eun Sung Lee; Youngjun Jang; Seokhwan Kim; Jinjoo Han; Hyun-Jung Choi; Ki Soo Park (Chemical Engineering Journal, 2023)

The effects of dyes and bleaches on the sorption and desorption of trace elements in human hair - Ji-Yu Shim; Han-Seul Lee; Woo-Jin Shin; Sanghee Park; Hye-Bin Choi; Hyung Seon Shin; Kwang-Sik Lee (Environmental Geochemistry and Health, 2023)

Evaluating ecotoxicological assays for comprehensive risk assessment of toxic metals present in industrial wastewaters in the Republic of Korea - Jihae Park; Kisik Shin; Hojun Lee; Soyeon Choi; Geonhee Kim; Stephen Depuydt; Jonas De Saeger; Philippe M. Heynderickx; Di Wu; Jana Asselman; Colin Janssen; Taejun Han (Science of The Total Environment, 2023)

Machine learning in establishing the stage–discharge rating curve of an irrigation canal - Yen-Chang Chen; Han-Chung Yang; Shin-Ping Lee; Cheng-Hsuan Ho (Paddy and Water Environment, 2023)

Evaluation of dryout region in a heap-like debris bed formed in an APR1400 pre-flooded reactor cavity - Hanbee Na; Ji-Hun Kim; Dong-Ho Shin; Han-Chul Kim; Sok Chul Kim (Annals of Nuclear Energy, 2023)

Regime shift increase in East Asia's summer extreme hot day frequency across the late 1990s - Yong‐Han Lee; Sang‐Wook Yeh; Jin‐Sil Hong; Jongsoo Shin; Soon‐Il An (International Journal of Climatology, 2023)
Here we analysed the long‐term change in extreme hot days (EHDs) in East Asia during boreal summer (June–July–August) since 1979, where EHDs was defined as days exceeding or equalling the 90th percentile threshold of the climatological (1991–2020) daily and . EHDs frequency occurrence in East Asia during summer showed not only an increasing trend but also a distinct regime shift increase since the late 1990s. Based on this regime shift, we divided these years into two periods, P1 (1979–1998) and P2 (1999–2021), and found that different physical processes operated for each period's EHDs variability. P2's EHDs was related to the stationary wave originating from both the North Atlantic Ocean and the Indo‐Pacific warm pool, but these influences did not appear in P1. To investigate whether the observed regime shift increase was caused by natural variability or greenhouse gas concentration increases, we conducted a CO 2 quadrupling experiment as well as a present‐day experiment with a fixed CO 2 concentration using the Community Earth System Model with 28 ensemble members. We demonstrated that the regime shift increase of East Asian EHDs occurrences was due to increasing greenhouse gas concentrations. We further discussed the influence of Arctic sea ice reduction due to global warming on EHDs occurrences in East Asia.

Seismic airgun sound propagation in shallow water of the East Siberian shelf and its prediction with the measured source signature - Dong-Gyun Han; Sookwan Kim; Martin Landrø; Wuju Son; Dae Hyeok Lee; Young Geul Yoon; Jee Woong Choi; Eun Jin Yang; Yeonjin Choi; Young Keun Jin; Jong Kuk Hong; Sung-Ho Kang; et al. (Frontiers in Marine Science, 2023)
Seismic airgun sound was measured with an autonomous passive acoustic recorder as a function of distance from 18.6 to 164.2 km in shallow water (<70 m) at the continental shelf of the East Siberian Sea in September 2019. The least-square regression curves were derived in the zero-to-peak sound pressure level, sound exposure level, and band level in a frequency range between 10 and 300 Hz using the initial amplitude scaled from the near-field hydrophone data. In addition, propagation modeling based on the parabolic equation with the measured source spectrum was performed for range-dependent bathymetry, and the results were compared with the band level of the measurements. The sediment structure of the measurement area was a thin layer of iceberg-scoured postglacial mud overlying a fast bottom with high density based on grounding events of past ice masses. The observed precursor arrivals, modal dispersion, and rapid decrease in spectrum level at low frequencies can be explained by the condition of the high-velocity sediment. Our results can be applied to studies on the inversion of ocean boundary conditions and measurement geometry and basic data for noise impact assessment.

Quaternary ammonium compounds of emerging concern: Classification, occurrence, fate, toxicity and antimicrobial resistance - Sanjeeb Mohapatra; Lin Yutao; Shin Giek Goh; Charmaine Ng; You Luhua; Ngoc Han Tran; Karina Yew-Hoong Gin (Journal of Hazardous Materials, 2023)

Characteristics of insecticidal substances from the entomopathogenic fungus Metarhizium pinghaense 15R against cotton aphid in Korea - InJi Heo; Seulki Kim; Gui Hwan Han; Seonghun Im; Jeong Won Kim; Dong Young Hwang; Ji Won Jang; Jin Young Lee; Soo Dong Woo; Tae Young Shin (Journal of Asia-Pacific Entomology, 2023)

Injectable remodeling hydrogels derived from alendronate-tethered alginate calcium complex for enhanced osteogenesis - Han-Sem Kim; JunHwee Jang; Jun-Sung Oh; Eun-Jung Lee; Cheol-Min Han; Ueon Sang Shin (Carbohydrate Polymers, 2023)

Alteration in Cerebral Metabolism in a Rodent Model of Acute Sub-lethal Cyanide Poisoning - Oladunni Alomaja; Frances S. Shofer; John C. Greenwood; Sarah Piel; Carly Clayman; Clementina Mesaros; Shih-Han Kao; Samuel S. Shin; Johannes K. Ehinger; Todd J. Kilbaugh; David H. Jang (Journal of Medical Toxicology, 2023)

Elucidation of microbial interactions, dynamics, and keystone microbes in high pressure anaerobic digestion - Ajay Thapa; Jeong-Hoon Park; Seung Gu Shin; Hong-Mok Jo; Min-Sang Kim; Yeongmi Park; Uijeong Han; Si-Kyung Cho (Science of The Total Environment, 2023)

Photochemical and microbial transformation of particulate organic matter depending on its source and size - Han-Saem Lee; Jin Hur; Hyun-Sang Shin (Science of The Total Environment, 2023)

Effects of temperature and starvation on life history traits and fatty acid profiles of the Antarctic copepod Tigriopus kingsejongensis - Deok-Seo Yoon; Hyuntae Choi; Alaa El-Din H. Sayed; Kyung-Hoon Shin; Joung Han Yim; Sanghee Kim; Min-Chul Lee; Jae-Seong Lee (Regional Studies in Marine Science, 2023)

Metal-oxide nanocomposite catalyst simultaneously boosts the oxygen reduction reactivity and chemical stability of solid oxide fuel cell cathode - SungHyun Jeon; Jongsu Seo; Jeong Woo Shin; Sungje Lee; Han Gil Seo; Siwon Lee; Nikolai Tsvetkov; Jinwook Kim; Jihwan An; WooChul Jung (Chemical Engineering Journal, 2023)

A mechanism-based understanding of altered drug pharmacokinetics by gut microbiota - Aneela Gulnaz; Ji-Eun Chang; Han-Joo Maeng; Kwang-Hee Shin; Kyeong-Ryoon Lee; Yoon-Jee Chae (Journal of Pharmaceutical Investigation, 2023)

Factors governing seawater carbonate dynamics in a macroalgal habitat - Ja-Myung Kim; Kitack Lee; In-Seong Han; Miok Kim; Ju-Hyoung Kim; Tae-Hoon Kim; HyunKyum Kim; Byung Hee Jeon; Kyoungsoon Shin (Frontiers in Marine Science, 2022)
Photosynthetic organisms shift the dynamics of surface pCO 2 driven by the sea surface temperature change (thermodynamic driver) by assimilating inorganic C from seawater. Here we measured net C uptake in a macroalgal habitat of coastal Korea for two years (2019-2020) and found that the macroalgal habitat contributed 5.8 g C m −2 month −1 of the net C uptake during the growing period (the cooling period, September−May). This massive C uptake changed the thermodynamics-driven seasonal dynamics such that the air−sea equilibrium of pCO 2 was pushed into disequilibrium. The surface pCO 2 dynamics during the cooling period was mostly influenced by the seasonal decrease in temperature and the proliferation of macroalgae, while the dynamics during the warming period (the stagnant period, June−August) closely followed that predicted based solely on the change in sea surface temperature (thermodynamic driver). In contrast to the phytoplankton-dominated off-shore waters (where phytoplankton populations are large in spring and summer), the impact of coastal macroalgae on surface pCO 2 dynamics was most pronounced during the cooling period, when the magnitude of pCO 2 change was as much as twice that resulting from temperature change. Our study shows that the distinctive features of the macroalgal habitat—in particular the seasonal temperature extremes (~18°C difference), the active macroalgal metabolism, and anthropogenic nutrient inputs—collectively influenced the seasonal decoupling of seawater and air pCO 2 dynamics.

The inflammatory signature in monocytes of Sjögren’s syndrome and systemic lupus erythematosus, revealed by the integrated Reactome and drug target analysis - Kyung Eun Lee; Seyoung Mun; Song-mi Kim; Wonseok Shin; Won Jung; Joon Paek; Jungnam Lee; Erin Hudson; Wesley H. Reeves; Kyudong Han; Seunghee Cha (Genes & Genomics, 2022)

Evaluation of anatomical and histological characteristics of human peripheral nerves: as an effort to develop an efficient allogeneic nerve graft - Jin-Hyung Im; Seung-Han Shin; Myeong-Kyu Lee; Sae-Rom Lee; Jae-Jin Lee; Yang-Guk Chung (Cell and Tissue Banking, 2022)

Use of lysates from pooled human mononuclear cells to activate CD3 T cells in humanized mice with low human cell engraftment efficiency - A-Reum Han; Jeoung Eun Lee; Seung Young Ko; Hyun Soo Shin; Jung Ho Im; Ji Yoon Lee; Dong Ryul Lee (In Vitro Cellular & Developmental Biology - Animal, 2022)

Rapid identification of SARS-CoV-2 in the point-of-care using digital PCR-based Dr. PCR™ Di20K COVID-19 Detection Kit without viral RNA extraction - Wonseok Shin; Cherl-Joon Lee; Yong-Moon Lee; Young-Bong Choi; Seyoung Mun; Kyudong Han (Genes & Genomics, 2022)

Hydrochloric acid-treated Bacillus subtilis ghosts induce IL-1 beta, IL-6, and TNF-alpha in murine macrophage - Young-Min Kim; Kwang-Su Lee; Won-Mun Kim; Min Kim; Han-Oh Park; Chang Won Choi; Joong-Soo Han; Shin-Young Park; Ki-Sung Lee (Molecular & Cellular Toxicology, 2022)
Background Bacterial ghosts (BGs) are empty cell envelopes commonly generated using Gram-negative bacteria; they represent a potential platform for efficient adjuvant and vaccine delivery systems. However, the efficient production of BGs from bacteria in a short period of time is challenging. Objective The purpose of this study was to investigate the possibility of producing BGs in the Gram-positive Bacillus subtilis using various chemicals, and the potential application of BGs as a novel immunomodulatory agent. Results In this study, Bacillus subtilis ghosts (BSGs) were generated, for the first time to the best of our knowledge, using the minimum inhibitory concentration (MIC) of hydrochloric acid (HCl; 6.25 mg/mL), sulfuric acid (H 2 SO 4 ; 3.125 mg/mL), and nitric acid (HNO 3 ; 6.25 mg/mL). Among the BSGs generated using these chemicals, HCl-induced BSGs were completely DNA-free as confirmed by real-time polymerase chain reaction. Scanning electron microscopy showed the formation of transmembrane lysis tunnel structures in HCl-induced BSGs. Murine macrophages exposed to the HCl-induced BSGs at a concentration of 1 × 10 5 CFU/mL showed a cell viability of 97.8%. Additionally, HCl-induced BSGs upregulated the expression of pro-inflammatory cytokines including interleukin (IL)-1β, tumor necrosis factor alpha, and IL-6. Furthermore, we found differences in the protein expression profiles between intact live bacteria and BSGs using two-dimensional electrophoresis coupled with peptide mass fingerprinting/matrix-assisted laser desorption/ionization-time of flight mass spectrometry analysis. Conclusion These data suggest that the HCl-induced BSGs may be potentially safe and effective candidates for inactivated bacterial vaccines and/or immunostimulants.

Correction to: Detailed clinical features and genotype–phenotype correlation in an OTOF-related hearing loss cohort in Japan - Yoh-ichiro Iwasa; Shin-ya Nishio; Hidekane Yoshimura; Akiko Sugaya; Yuko Kataoka; Yukihide Maeda; Yukihiko Kanda; Kyoko Nagai; Yasushi Naito; Hiroshi Yamazaki; Tetsuo Ikezono; Han Matsuda; et al. (Human Genetics, 2022)

Detailed clinical features and genotype–phenotype correlation in an OTOF-related hearing loss cohort in Japan - Yoh-ichiro Iwasa; Shin-ya Nishio; Hidekane Yoshimura; Akiko Sugaya; Yuko Kataoka; Yukihide Maeda; Yukihiko Kanda; Kyoko Nagai; Yasushi Naito; Hiroshi Yamazaki; Tetsuo Ikezono; Han Matsuda; et al. (Human Genetics, 2022)
Mutations in the OTOF gene are a common cause of hereditary hearing loss and the main cause of auditory neuropathy spectrum disorder (ANSD). Although it is reported that most of the patients with OTOF mutations have stable, congenital or prelingual onset severe-to-profound hearing loss, some patients show atypical clinical phenotypes, and the genotype–phenotype correlation in patients with OTOF mutations is not yet fully understood. In this study, we aimed to reveal detailed clinical characteristics of OTOF -related hearing loss patients and the genotype–phenotype correlation. Detailed clinical information was available for 64 patients in our database who were diagnosed with OTOF -related hearing loss. As reported previously, most of the patients (90.6%) showed a “typical” phenotype; prelingual and severe-to-profound hearing loss. Forty-seven patients (73.4%) underwent cochlear implantation surgery and showed successful outcomes; approximately 85–90% of the patients showed a hearing level of 20–39 dB with cochlear implant and a Categories of Auditory Performance (CAP) scale level 6 or better. Although truncating mutations and p.Arg1939Gln were clearly related to severe phenotype, almost half of the patients with one or more non-truncating mutations showed mild-to-moderate hearing loss. Notably, patients with p.His513Arg, p.Ile1573Thr and p.Glu1910Lys showed “true” auditory neuropathy-like clinical characteristics. In this study, we have clarified genotype–phenotype correlation and efficacy of cochlear implantation for OTOF -related hearing loss patients in the biggest cohort studied to date. We believe that the clinical characteristics and genotype–phenotype correlation found in this study will support preoperative counseling and appropriate intervention for OTOF -related hearing loss patients.

A hypotonic gel-forming eye drop provides enhanced intraocular delivery of a kinase inhibitor with melanin-binding properties for sustained protection of retinal ganglion cells - Yoo Chun Kim; Henry T. Hsueh; Matthew D. Shin; Cynthia A. Berlinicke; Hyounkoo Han; Nicole M. Anders; Avelina Hemingway; Kirby T. Leo; Renee Ti Chou; HyeYoung Kwon; Matthew B. Appell; Usha Rai; et al. (Drug Delivery and Translational Research, 2022)

Establishment of bioreactor cultures for the production of chlorogenic acid and ferulic acid from adventitious roots by optimization of culture conditions in Angelica acutiloba (Siebold & Zucc.) Kitag - Ho-Dong Hwang; Jong-Eun Han; Hosakatte Niranjana Murthy; Hyuk Joon Kwon; Gun-Myung Lee; Jae-Hyuk Shin; So-Young Park (Plant Biotechnology Reports, 2022)

The SEEL motif and members of the MYB-related REVEILLE transcription factor family are important for the expression of LORELEI in the synergid cells of the Arabidopsis female gametophyte - Jennifer A. Noble; Alex Seddon; Sahra Uygun; Ashley Bright; Steven E. Smith; Shin-han Shiu; Ravishankar Palanivelu (Plant Reproduction, 2022)

Differences in Cerebral Distribution between Imipramine and Paroxetine via Membrane Transporters at the Rat Blood-Brain Barrier - Shin-ichi Akanuma; Myeongrae Han; Yuka Murayama; Yoshiyuki Kubo; Ken-ichi Hosoya (Pharmaceutical Research, 2022)

Utility of plasma cell-free DNA detection using homobifunctional imidoesters using a microfluidic system for diagnosing active tuberculosis - Joung Ha Park; Bonhan Koo; Min Jae Kim; Hyo Joo Lee; Hye-Hee Cha; Ji Yeun Kim; Sei Won Lee; Yong Shin; Sung-Han Kim (Infectious Diseases, 2022)

Comparison of two different decellularization methods for processed nerve allograft - Han-Vit Kang; Jin-Hyung Im; Yang-Guk Chung; Eun-Young Shin; Myeong-kyu Lee; Joo-Yup Lee (Cell and Tissue Banking, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Dietary supplementations of Bacillus probiotic improve digestibility, growth performance, innate immunity, and water ammonia level for Pacific white shrimp, Litopenaeus vannamei - Chorong Lee; Soohwan Kim; Jaehyeong Shin; Min-Gi Kim; Buddhi E. Gunathilaka; Sung Hun Kim; Ji Eun Kim; Seung-Cheol Ji; Jee Eun Han; Kyeong-Jun Lee (Aquaculture International, 2021)

Diagnostic evaluation of qRT-PCR-based kit and dPCR-based kit for COVID-19 - Cherl-Joon Lee; Wonseok Shin; Seyoung Mun; Minjae Yu; Young-Bong Choi; Dong Hee Kim; Kyudong Han (Genes & Genomics, 2021)

Tumor Microenvironment Modulating Functional Nanoparticles for Effective Cancer Treatments - Seungyong Shin; Jiyoung Lee; Jieun Han; Fangyuan Li; Daishun Ling; Wooram Park (Tissue Engineering and Regenerative Medicine, 2021)

Effectiveness and Biocompatibility of Decellularized Nerve Graft Using an In Vivo Rat Sciatic Nerve Model - Dong Hyun Kim; Seung-Han Shin; Myeong-Kyu Lee; Jae-Jin Lee; Jae Kwang Kim; Yang-Guk Chung (Tissue Engineering and Regenerative Medicine, 2021)

Coastal sea-surface wave measurements using software-based GPS reflectometers in Lanyu, Taiwan - Lung-Chih Tsai; Shin-Yi Su; Hwa Chien; Chao-Han Liu; Harald Schuh; Jens Wickert; Mohamad Mahdi Alizadeh (GPS Solutions, 2021)

Dietary Shifts and Risks of Artifact Ingestion for Argentine Shortfin Squid Illex argentinus in the Southwest Atlantic - Ssu-Wei Chang; Ruei-Gu Chen; Tsung-Han Liu; Yao-Chang Lee; Chih-Shin Chen; Tai-Sheng Chiu; Chia-Ying Ko (Frontiers in Marine Science, 2021)
Cephalopods play an important role in both ecology and fisheries. Variations in the dietary compositions of squids with large populations further promote interactions between different trophic levels in marine ecosystems. Moreover, due to marine pollution, squids are also at risks of artifact ingestion, and there is limited understanding about the influence of artifacts on the feeding behavior of squids. We examined 296 stomachs of the Argentine shortfin squid Illex argentinus collected through commercial catches across the Southwest Atlantic from February to April of 2018 and 2019 to establish the monthly dietary compositions and risks of artifact ingestion. The results supported typical observations that the Argentine shortfin squids switched from a diet dominated by crustaceans at small sizes to consuming larger prey, predominantly fishes and/or cephalopods, at large sizes during their growth and southward migration. Significantly higher consumption of fishes was observed in recent years compared with that observed in other studies since 1992. The ingested artifacts examined were composed of plastic and non-plastic materials. Artifacts were observed in 19.9% of the total number of stomachs, with 20.5% of the empty stomachs containing artifact remains. The results indicate that although the main dietary compositions of the Argentine shortfin squid maintain the taxonomic groups of prey compositions, the dietary structure, i.e., composition percentage, is varying. The detection of artifacts suggests that environmental monitoring is needed in this region in order to manage and conserve the squid and safeguard aquatic food safety.

Inactivation of the β (1, 2)-xylosyltransferase and the α (1, 3)-fucosyltransferase gene in rice (Oryza sativa) by multiplex CRISPR/Cas9 strategy - Jae-Wan Jung; Jun-Hye Shin; Won-Kyung Lee; Hilal Begum; Chan-Hong Min; Mi-Hwa Jang; Han-Bin Oh; Moon-Sik Yang; Seong-Ryong Kim (Plant Cell Reports, 2021)

Aquaculture Farming Effect on Benthic Respiration and Nutrient Flux in Semi-Enclosed Coastal Waters of Korea - Sung-Han Kim; Jae-Seong Lee; Kyung-Tae Kim; Hyung-Chul Kim; Won-Chan Lee; Dongmun Choi; Sang-Hwa Choi; Jae-Hoon Choi; Hyo-Jin Lee; Jae-Hyuk Shin (Journal of Marine Science and Engineering, 2021)
Sediment oxygen demand (SOD) and benthic nutrient fluxes (BNFs) were measured using an in situ benthic chamber at a fish farm (FF), oyster farm (OF), and controls (FF-C and OF-C) to assess the impact of aquaculture activities on organic carbon (OC) and nutrients cycles in coastal waters of Korea. The SOD at FF and OF ranged from 60 ± 2 to 157 ± 3 mmol m−2 d−1 and from 77 ± 14 to 84 ± 16 mmol m−2 d−1, respectively, more than five times those of the control sites. The SOD at farm sites is highly correlated with fish stock and food input, suggesting that excess feed input is an important control factor for OC remineralization. The combined analysis of sediment trap and SOD indicates that most of the deposited OC oxidized in the sediment and/or was laterally transported by the current before being buried in the sediment. The benthic nutrient fluxes at farms ranged from 5.45 to 8.95 mmol N m−2 d−1 for nitrogen and from 0.51 to 1.67 mmol P m−2 d−1 for phosphate, respectively, accounting for 37–270% and 52–804% of the N and P required for primary production in the water column. These results indicate that aquaculture farming may profoundly impact biogeochemical cycles in coastal waters.

Response of citrus to freezing tolerance differs depending on genotypes and growing conditions - Misun Kim; Seok Kyu Yun; Sang Suk Kim; YoSup Park; Jaeho Joa; Seunggab Han; Kihye Shin; Kwan Jeong Song (Horticulture, Environment, and Biotechnology, 2021)

Delayed association of acute particulate matter 2.5 air pollution exposure with loss of complexity in cardiac rhythm dynamics: insight from detrended fluctuation analysis - Tsung-Ying Tsai; Li-Wei Lo; Shin-Huei Liu; Wen-Han Cheng; Yu-Hui Chou; Wei-Lun Lin; Yenn-Jiang Lin; Shih-Lin Chang; Yu-Feng Hu; Fa-Po Chung; Jo-Nan Liao; Tze-Fan Chao; et al. (Environmental Science and Pollution Research, 2021)

Anthropogenic nitrogen is changing the East China and Yellow seas from being N deficient to being P deficient - Ji‐Young Moon; Kitack Lee; Weol‐Ae Lim; Eunil Lee; Minhan Dai; Yang‐Ho Choi; In‐Seong Han; Kyoungsoon Shin; Ja‐Myung Kim; Jinho Chae (Limnology and Oceanography, 2021)
Addition of the increased anthropogenic nitrogen (NO x and NH y ) emitted from northeast Asian countries to the Yellow and East China seas and coastal waters around Korea has resulted in an unparalleled increase in the nitrate (N) concentration relative to the phosphate (P) and silicate (Si) concentrations in the upper ocean. We found that for the Yellow Sea the increase in N over P was largely explained by increased atmospheric nitrogen deposition, whereas for the northern East China Sea, downstream of the Changjiang River plume, the trend in N increase relative to P was more associated with a change in the combined input of nutrients from atmospheric deposition and riverine discharges. In contrast, the dynamics of the N to P relationship in the southern East China Sea was largely controlled by a change in the intrusion intensity of the Kuroshio Current, which has a low N : P ratio. The disproportionate and persistent input of nutrients to the marine waters of this region over the past four decades has transformed extensive areas from being N deficient to being P deficient, and has concurrently decreased the concentration of Si relative to N. In coastal waters around Korea in particular, these shifts in the nutrient regime have been accompanied by a change from diatom‐dominated to dinoflagellate‐dominated blooms. Given the complexity of coastal ecosystems, the associations between changes in nutrient regimes and biological changes need to be investigated in other coastal areas receiving increasing loads of anthropogenic nitrogen.

Electrospun Microvasculature for Rapid Vascular Network Restoration - Je-Hyun Han; Ung Hyun Ko; Hyo Jun Kim; Seunggyu Kim; Jessie S. Jeon; Jennifer H. Shin (Tissue Engineering and Regenerative Medicine, 2021)

Inhibition of EGR-1-dependent MMP1 transcription by ethanol extract of Ageratum houstonianum in HaCaT keratinocytes - Soon Young Shin; Dongsoo Koh; Yoongho Lim; Young Han Lee (Molecular Biology Reports, 2021)

Muscle differentiation induced by p53 signaling pathway-related genes in myostatin-knockout quail myoblasts - Jeong-Woong Park; Jeong Hyo Lee; Ji Seon Han; Seung Pyo Shin; Tae Sub Park (Molecular Biology Reports, 2020)

Transcriptomic analysis of the effect of (E)-3-(3,5-dimethoxyphenyl)-1-(2-methoxyphenyl) prop-2-en-1-one (DPP23) on reactive oxygen species generation in MIA PaCa-2 pancreatic cancer cells - Hongnam Sim; Euitaek Jung; Da Hyun Lee; Ji Hye Choi; Young Han Lee; Soon Young Shin (Genes & Genomics, 2020)

Screening for twenty-eight target anabolic-androgenic steroids in protein supplements using QuEChERS extraction followed by liquid chromatography-tandem mass spectrometry - Ji Hyun Lee; Ji Hye Han; A. Young Min; Hyungil Kim; Dongwoo Shin (Food Additives & Contaminants: Part A, 2020)

Development and validation of LC-MS/MS method with QuEChERS clean-up for detecting cannabinoids in foods and dietary supplements - Ji Hyun Lee; A Young Min; Ji Hye Han; Yoon Ji Yang; Hyungil Kim; Dongwoo Shin (Food Additives & Contaminants: Part A, 2020)

Regulation of pro-opiomelanocortin (POMC) gene transcription by interleukin-31 via early growth response 1 (EGR-1) in HaCaT keratinocytes - Hyunjin Yeo; Sung Shin Ahn; Young Han Lee; Soon Young Shin (Molecular Biology Reports, 2020)

A new approach to the restoration of seaweed beds using Sargassum fulvellum - Sang Mok Jung; Ji Hyun Lee; Seung Hee Han; Won Bin Jeon; Ga Yeon Kim; Sinyang Kim; Seongju Kim; Hwa-Rim Lee; Dong Soo Hwang; Sungjune Jung; Jongdae Lee; Hyun Woung Shin (Journal of Applied Phycology, 2020)

Effects of stocking density on the productivity and nutrient removal of Agarophyton vermiculophyllum in Paralichthys olivaceus biofloc effluent - Sook Kyung Shin; Su-Kyoung Kim; Jun-Hwan Kim; Taejun Han; Charles Yarish; Jang K. Kim (Journal of Applied Phycology, 2020)

Improving regional groundwater storage estimates from GRACE and global hydrological models over Tasmania, Australia - Wenjie Yin; Tongqing Li; Wei Zheng; Litang Hu; Shin-Chan Han; Natthachet Tangdamrongsub; Michal Šprlák; Zhiyong Huang (Hydrogeology Journal, 2020)

GRACE gravitational measurements of tsunamis after the 2004, 2010, and 2011 great earthquakes - Khosro Ghobadi-Far; Shin-Chan Han; Sébastien Allgeyer; Paul Tregoning; Jeanne Sauber; Saniya Behzadpour; Torsten Mayer-Gürr; Nico Sneeuw; Emile Okal (Journal of Geodesy, 2020)
The 2004 Sumatra, 2010 Maule, and 2011 Tohoku great earthquakes triggered tsunamis as large as a few decimeters over a few 100 km in the open ocean. The transient ocean mass redistribution propagating as tsunamis changed the Earth’s gravity field enough to perturb the GRACE satellites’ orbits at ~ 500 km above the surface. The on-board microwave ranging system detected inter-satellite acceleration anomalies of up to 1.0–4.0 nm/s 2 . There is good agreement between GRACE measurements and tsunami models for the three events. Complementarily to buoys, ocean bottom pressure sounders, and satellite altimeters, GRACE is sensitive to the long-wavelength spatial scale of tsunamis and provides an independent source of information for assessing alternate early earthquake and tsunami models. Our study demonstrates an innovative way of applying GRACE and GRACE Follow-On data to detect transient geophysical mass changes which cannot be observed by the conventional monthly Level-2 and mascon solutions.

Meteorological Products of Geo-KOMPSAT 2A (GK2A) Satellite - Sung-Rae Chung; Myoung-Hwan Ahn; Kyung-Soo Han; Kyu-Tae Lee; Dong-Bin Shin (Asia-Pacific Journal of Atmospheric Sciences, 2020)

Association between tooth loss and gray matter volume in cognitive impairment - Chia-Shu Lin; Hsiao-Han Lin; Shin-Woei Fann; Wei-Ju Lee; Ming-Lun Hsu; Shuu-Jiun Wang; Jong-Ling Fuh (Brain Imaging and Behavior, 2020)

Application of NanoString technologies in angioimmunoblastic T cell lymphoma - Wonseok Shin; Seyoung Mun; Seungkyu Choi; Kyudong Han (Genes & Genomics, 2020)

Taxonomic study of three new Antarctic Asterochloris (Trebouxio-phyceae) based on morphological and molecular data - Jong Im Kim; Yong Jun Kim; Seung Won Nam; Jae Eun So; Soon Gyu Hong; Han-Gu Choi; Woongghi Shin (Algae, 2020)

Diverse Gene Expressions in the Prediction of Cuprizone-Induced Demyelination - Seung Ro Han; Yun Hee Kang; Seung-Min Yoo; Myung-Shin Lee; Seung-Hoon Lee (Neurotoxicity Research, 2020)

A multidisciplinary assessment of the impact of spilled acids on geoecosystems: an overview - Sung Pil Hyun; Doyun Shin; Hee Sun Moon; Young-Soo Han; Seonjin Ha; Yoonho Lee; Eunhee Lee; Hyun Jung; Yu Sik Hwang (Environmental Science and Pollution Research, 2020)

Circadian modulation of the cardiac proteome underpins differential adaptation to morning and evening exercise training: an LC-MS/MS analysis - Dae Yun Seo; Chang Shin Yoon; Louise Anne Dizon; Sung Ryul Lee; Jae Boum Youm; Won Suk Yang; Hyo-Bum Kwak; Tae Hee Ko; Hyoung Kyu Kim; Jin Han; Robin A McGregor (Pflügers Archiv - European Journal of Physiology, 2020)

Removal of various contaminants from water by renewable lignocellulose-derived biosorbents: a comprehensive and critical review - Hai Nguyen Tran; Hoang Chinh Nguyen; Seung Han Woo; Tien Vinh Nguyen; Saravanamuthu Vigneswaran; Ahmad Hosseini-Bandegharaei; Jörg Rinklebe; Ajit Kumar Sarmah; Andrei Ivanets; Guilherme Luiz Dotto; Tho Truong Bui; Ruey-Shin Juang; et al. (Critical Reviews in Environmental Science and Technology, 2019)

The protective effects of echinochrome A structural analogs against oxidative stress and doxorubicin in AC16 cardiomyocytes - Chang Shin Yoon; Hyoung Kyu Kim; Natalia P. Mishchenko; Elena A. Vasileva; Sergey A. Fedoreyev; Olga P. Shestak; Nadezhda N. Balaneva; Vyacheslav L. Novikov; Valentin A. Stonik; Jin Han (Molecular & Cellular Toxicology, 2019)

Comparison of library construction kits for mRNA sequencing in the Illumina platform - Yong-Soo Park; Songmi Kim; Dong-Guk Park; Dong Hee Kim; Kyeong-Wook Yoon; Wonseok Shin; Kyudong Han (Genes & Genomics, 2019)

Fipronil induces apoptosis and cell cycle arrest in porcine oocytes during in vitro maturation - Wenjun Zhou; Ying-Jie Niu; Zheng-Wen Nie; Yong-Han Kim; Kyung-Tae Shin; Jing Guo; Xiang-Shun Cui (Apoptosis, 2019)

Increased Diagnostic Yield of Spastic Paraplegia with or Without Cerebellar Ataxia Through Whole-Genome Sequencing - Aryun Kim; Kishore R. Kumar; Ryan L. Davis; Amali C. Mallawaarachchi; Velimir Gayevskiy; Andre E. Minoche; Zachary Walls; Han-Joon Kim; Mihee Jang; Mark J. Cowley; Ji-Hyun Choi; Chaewon Shin; et al. (The Cerebellum, 2019)

Increase of Hspa1a and Hspa1b genes in the resting B cells of Sirt1 knockout mice - Younghwan Han; Yujin Kang; Jaemin Yu; Seong-Lan Yu; Hwan-Woo Park; Jongdae Shin; Seok-Rae Park; Jaeku Kang (Molecular Biology Reports, 2019)

The effect of caffeine on cerebral metabolism during alpha-chloralose anesthesia differs from isoflurane anesthesia in the rat brain - Shin-Lei Peng; Han Chiu; Chun-Yi Wu; Chiun-Wei Huang; Yi-Hsiu Chung; Cheng-Ting Shih; Wu-Chung Shen (Psychopharmacology, 2019)

Design, synthesis, and biological evaluation of polyphenols with 4,6-diphenylpyrimidin-2-amine derivatives for inhibition of Aurora kinase A - Young Han Lee; Jihyun Park; Seunghyun Ahn; Youngshim Lee; Junho Lee; Soon Young Shin; Dongsoo Koh; Yoongho Lim (DARU Journal of Pharmaceutical Sciences, 2019)

Methoxetamine Induces Cytotoxicity in H9c2 Cells: Possible Role of p21 Protein (Cdc42/Rac)-Activated Kinase 1 - Kyung Sik Yoon; Sun Mi Gu; Santosh Lamichhane; Kyoung Moon Han; Jisoon Shin; Young-Hoon Kim; Soo Kyung Suh; Hye Jin Cha; Jaesuk Yun (Cardiovascular Toxicology, 2019)

Repositioning of the antipsychotic drug TFP for sepsis treatment - Jung Hwa Park; Hyun Jin Park; Sung Eun Lee; Young Seob Kim; Gun-Young Jang; Hee Dong Han; In Duk Jung; Kyung Chul Shin; Young Min Bae; Tae Heung Kang; Yeong-Min Park (Journal of Molecular Medicine, 2019)

Inhibition of TNFα-induced interleukin-6 gene expression by barley (Hordeum vulgare) ethanol extract in BV-2 microglia - Jihye Choi; Juhwan Kim; Dong Yeong Min; Euitaek Jung; Yoongho Lim; Soon Young Shin; Young Han Lee (Genes & Genomics, 2019)

Leptin is a direct transcriptional target of EGR1 in human breast cancer cells - JuHwan Kim; Euitaek Jung; Jihye Choi; Dong Yeong Min; Young Han Lee; Soon Young Shin (Molecular Biology Reports, 2019)

Genetic diversity of kiwifruit (Actinidia spp.), including Korean native A. arguta, using single nucleotide polymorphisms derived from genotyping-by-sequencing - Sewon Oh; Mockhee Lee; Keumsun Kim; Hyeondae Han; Kyungho Won; Yong-Bum Kwack; Hyunsuk Shin; Daeil Kim (Horticulture, Environment, and Biotechnology, 2019)

Investigation of Hanwoo-specific structural variations using whole-genome sequencing data - Jangho Park; Wonseok Shin; Seyoung Mun; Man Hwan Oh; Dajeong Lim; Dong-Yep Oh; Youngjune Bhak; Jong Bhak; Yong-Soo Park; Kyudong Han (Genes & Genomics, 2019)

Quantitative investigation of Enteromyxum leei (Myxozoa: Myxosporea) infection and relative condition factor in cultured olive flounder Paralichthys olivaceus (Temminck and Schlegel) - Sang Phil Shin; Han Chang Sohn; Chang Nam Jin; Bong Jo Kang; Jehee Lee (Journal of Fish Diseases, 2019)
Enteromyxum leei has been reported to cause emaciation disease in various fish species. To determine the effect of parasite intensity on cultured olive flounder Paralichthys olivaceus , we investigated the relationship between the relative condition factor ( rCF = CF /standard CF × 100) and parasite load with quantitative polymerase chain reaction ( qPCR ) and the challenge test. A total of 57 cultured olive flounders were obtained from 11 fish farms and divided into five groups based on their rCF . We investigated the parasite intensity in the posterior intestine of the fish. The parasite load was closely matched to severe loss of body weight. In addition, olive flounders were inoculated either orally or anally with intestinal scrapings of infected fish or phosphate‐buffered saline. The fish were reared at natural water temperature and transferred to different tanks, and the water temperature was adjusted to 20°C after 6 weeks of inoculation. When the water temperature was increased to 20°C, the rCF decreased in the experimentally infected group. The results demonstrated that qPCR can be utilized to determine the relative abundance of E. leei in olive flounders and water temperature is an important factor to track the progress of the emaciation disease.

Temporal variation in bacterial and methanogenic communities of three full-scale anaerobic digesters treating swine wastewater - Gyuseong Han; Seung Gu Shin; Kyungjin Cho; Joonyeob Lee; Woong Kim; Seokhwan Hwang (Environmental Science and Pollution Research, 2019)

Correction to: Combination of photodynamic therapy (PDT) and anti-tumor immunity in cancer therapy - Hee Sook Hwang; Heejun Shin; Jieun Han; Kun Na (Journal of Pharmaceutical Investigation, 2019)

A case of interdigitating dendritic cell sarcoma studied by whole-exome sequencing - Ki Hwan Hong; Soyoung Song; Wonseok Shin; Keunsoo Kang; Chun-Sung Cho; Yong Tae Hong; Kyudong Han; Jeong Hwan Moon (Genes & Genomics, 2018)

Global morphology of ionospheric sporadic E layer from the FormoSat-3/COSMIC GPS radio occultation experiment - Lung-Chih Tsai; Shin-Yi Su; Chao-Han Liu; Harald Schuh; Jens Wickert; Mohamad Mahdi Alizadeh (GPS Solutions, 2018)

Alterations of ATP-sensitive K+ channels in human umbilical arterial smooth muscle during gestational diabetes mellitus - Hongliang Li; Sung Eun Shin; Mi Seon Seo; Jin Ryeol An; Kwon-Soo Ha; Eun-Taek Han; Seok-Ho Hong; Jeeyoung Kim; Mi-Jin Yim; Jeong Min Lee; Tae Gyu An; Jihan Jeon; et al. (Pflügers Archiv - European Journal of Physiology, 2018)

Land cover change explains the increasing discharge of the Paraná River - Eunjee Lee; Angela Livino; Shin-Chan Han; Ke Zhang; John Briscoe; Jerson Kelman; Paul Moorcroft (Regional Environmental Change, 2018)

Genetic characteristics of Y-chromosome short tandem repeat haplotypes from cigarette butt samples presumed to be smoked by North Korean men - Kyu-Sik Jeong; Heejin Shin; Sung-Jin Lee; Hyo-Sook Kim; Jang-Yong Kim; Myun-Soo Han; Yang-Han Lee; Ki-Won Park; Byung-Won Chun (Genes & Genomics, 2018)

Inhibition of the Voltage-Dependent K+ Current by the Tricyclic Antidepressant Desipramine in Rabbit Coronary Arterial Smooth Muscle Cells - Sung Eun Shin; Hongliang Li; Jin Ryeol An; Mi Seon Seo; Sung Hun Na; Won-Kyo Jung; Amy L. Firth; Kwon-Soo Ha; Eun-Taek Han; Seok-Ho Hong; Il-Whan Choi; Won Sun Park (Cardiovascular Toxicology, 2018)

Development of an Operational Hybrid Data Assimilation System at KIAPS - In-Hyuk Kwon; Hyo-Jong Song; Ji-Hyun Ha; Hyoung-Wook Chun; Jeon-Ho Kang; Sihye Lee; Sujeong Lim; Youngsoon Jo; Hyun-Jun Han; Hanbyeol Jeong; Hui-Nae Kwon; Seoleun Shin; et al. (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Comparison of Mutagenic Activities of Various Ultra-Fine Particles - Chang Gyun Park; Hyun Ki Cho; Han Jae Shin; Ki Hong Park; Heung Bin Lim (Toxicological Research, 2018)

Phylogeography of the Asian lesser white-toothed shrew, Crocidura shantungensis, in East Asia: role of the Korean Peninsula as refugium for small mammals - Seo-Jin Lee; Mu-Yeong Lee; Liang-Kong Lin; Y. Kirk Lin; Yuchun Li; E-Hyun Shin; Sang-Hoon Han; Mi-Sook Min; Hang Lee; Kyung Seok Kim (Genetica, 2018)

Identification of quantitative trait loci associated with drought tolerance traits in rice (Oryza sativa L.) under PEG and field drought stress - Bing Han; Jiao Wang; Yafei Li; Xiaoding Ma; Sumin Jo; Di Cui; Yanjie Wang; Dongsoo Park; Youchun Song; Guilan Cao; Xingsheng Wang; Jianchang Sun; et al. (Euphytica, 2018)

Identification of QTLs associated with heat tolerance at the heading and flowering stage in rice (Oryza sativa L.) - Mao-mao Li; Xia Li; Li-qin Yu; Jin-wen Wu; Hui Li; Jin Liu; Xiao-ding Ma; Su-min Jo; Dong-Soo Park; Youchun Song; Dongjin Shin; Long-zhi Han (Euphytica, 2018)

New insights on the green synthesis of metallic nanoparticles using plant and waste biomaterials: current knowledge, their agricultural and environmental applications - Rijuta Ganesh Saratale; Ganesh Dattatraya Saratale; Han Seung Shin; Jaya Mary Jacob; Arivalagan Pugazhendhi; Mukesh Bhaisare; Gopalakrishanan Kumar (Environmental Science and Pollution Research, 2018)

Exploiting fruit byproducts for eco-friendly nanosynthesis: Citrus × clementina peel extract mediated fabrication of silver nanoparticles with high efficacy against microbial pathogens and rat glial tumor C6 cells - Rijuta Ganesh Saratale; Han-Seung Shin; Gopalakrishnan Kumar; Giovanni Benelli; Gajanan S. Ghodake; Yuan Yuan Jiang; Dong Su Kim; Ganesh Dattatraya Saratale (Environmental Science and Pollution Research, 2018)

Effects of Thermal Stress on the mRNA Expression of SOD, HSP90, and HSP70 in the Spotted Sea Bass (Lateolabrax maculatus) - Moon-Kyeong Shin; Ho-Ra Park; Won-Jun Yeo; Kyung-Nam Han (Ocean Science Journal, 2018)

Phospholipase D1 Signaling: Essential Roles in Neural Stem Cell Differentiation - Shin-Young Park; Joong-Soo Han (Journal of Molecular Neuroscience, 2018)

Combination of photodynamic therapy (PDT) and anti-tumor immunity in cancer therapy - Hee Sook Hwang; Heejun Shin; Jieun Han; Kun Na (Journal of Pharmaceutical Investigation, 2018)
Photodynamic therapy (PDT) is performed using a photosensitizer and light of specific wavelength in the presence of oxygen to generate singlet oxygen and reactive oxygen species(ROS) in the cancer cells. The accumulated photosensitizers in target sites induce ROS generation upon light activation, then the generated cytotoxic reactive oxygen species lead to tumor cell death via apoptosis or necrosis, and damages the target sites which results tumor destruction. As a consequence, the PDT-mediated cell death is associated with anti-tumor immune response. In this paper, the effects of PDT and immune response on tumors are reviewed. Activation of an immune response regarding the innate and adaptive immune response, interaction with immune cells and tumor cells that associated with antitumor efficacy of PDT are also discussed.

Integration of Bacterial Expansin on Agarolytic Complexes to Enhance the Degrading Activity of Red Algae by Control of Gelling Properties - Da Woon Jeong; Jeong Eun Hyeon; Young-Chul Joo; Sang Kyu Shin; Sung Ok Han (Marine Biotechnology, 2018)

A synthetic cannabinoid JWH-210 reduces lymphoid organ weights and T-cell activator levels in mice via CB2 receptors - Sun Mi Gu; Hyun Jin Lee; Tac-hyung Lee; Yun Jeong Song; Young-Hoon Kim; Kyoung-Moon Han; Jisoon Shin; Hye-Kyung Park; Hyung Soo Kim; Hye Jin Cha; Jaesuk Yun (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

A nationwide study of the incidence rate of herb-induced liver injury in Korea - Jung-Hyo Cho; Dal-Seok Oh; Sang-Hoon Hong; Heung Ko; Nam-Hun Lee; Sang-Eun Park; Chang-Woo Han; Seung-Mo Kim; Young-Chul Kim; Kang-San Kim; Chang-Won Choi; Seon-My Shin; et al. (Archives of Toxicology, 2017)

Decline patterns and risk assessment of 10 multi-class pesticides in young sprout amaranth (Amaranthus mangostanus) under greenhouse growing conditions - In Kyung Kim; Sung-Woo Kim; A. M. Abd El-Aty; Md. Musfiqur Rahman; Md. Humayun Kabir; Han Sol Lee; Hyung Suk Chung; Ji Hoon Jeong; Ho-Chul Shin; Jae-Han Shim (Environmental Science and Pollution Research, 2017)

Comparative In Vitro Biological Toxicity of Four Kinds of Air Pollution Particles - Han-Jae Shin; Hyun Gi Cho; Chang Kyun Park; Ki Hong Park; Heung Bin Lim (Toxicological Research, 2017)

Postural Stability Assessment in Patients with Mild Traumatic Brain Injury Complaining of Dizziness - Kai-Yun Chen; Shih-Wei Huang; Yen-Nung Lin; Chun-De Liao; Wen-Hsuan Hou; Tsan-Hon Liou; Yung-Hsiao Chiang; Shin-Han Tsai; Wen-Ta Chiu; Wei-Chun Hsu; Li-Fong Lin (Journal of Medical and Biological Engineering, 2017)

Dissipation kinetics, pre-harvest residue limits, and hazard quotient assessments of pesticides flubendiamide and fluopicolide in Korean melon (Cucumis melo L. var. makuwa) grown under regulated conditions in plastic greenhouses - Md. Humayun Kabir; A. M. Abd El-Aty; Md. Musfiqur Rahman; Sung-Woo Kim; Han Sol Lee; Hyung Suk Chung; Jung Ah Do; Ji Hoon Jeong; Byung-Joon Chang; Moon Ik Chang; Ho-Chul Shin; Jae-Han Shim (Environmental Science and Pollution Research, 2017)

Neuronal NOS Induces Neuronal Differentiation Through a PKCα-Dependent GSK3β Inactivation Pathway in Hippocampal Neural Progenitor Cells - Shin-Young Park; Min-Jeong Kang; Joong-Soo Han (Molecular Neurobiology, 2017)

Effects of temperature on growth and fatty acid synthesis in the cyclopoid copepod Paracyclopina nana - Seung-Hwi Lee; Min-Chul Lee; Jayesh Puthumana; Jun Chul Park; Sujin Kang; Jeonghoon Han; Kyung-Hoon Shin; Heum Gi Park; Ae-Son Om; Jae-Seong Lee (Fisheries Science, 2017)

Intracellular Remodeling and Accumulation of Aberrant Lysosomes in Differentiation of Tonsil-Derived Mesenchymal Stem Cells into Parathyroid-Like Cells - Young-Il Jo; Gyungah Kim; Yoon Mi Jin; Yoon Jeong Park; Han Su Kim; Yoon Shin Park (Tissue Engineering and Regenerative Medicine, 2017)

Applying spatial analysis techniques to assess the suitability of multipurpose uses of spring water in the Jiaosi Hot Spring Region, Taiwan - Cheng-Shin Jang; Han-Chen Huang (Environmental Monitoring and Assessment, 2017)

Lipid Emulsion Inhibits Apoptosis Induced by a Toxic Dose of Verapamil via the Delta-Opioid Receptor in H9c2 Rat Cardiomyoblasts - Seong-Ho Ok; Mun Hwan Choi; Il-Woo Shin; Soo Hee Lee; Sebin Kang; Jiah Oh; Jeong Yeol Han; Ju-Tae Sohn (Cardiovascular Toxicology, 2017)

Effects of biocontrol with an atyid shrimp (Caridina denticulata) and a bagrid catfish (Pseudobagrus fulvidraco) on toxic cyanobacteria bloom (Microcystis aeruginosa) in a eutrophic agricultural reservoir - Min-Seob Kim; Yeonjung Lee; Seongjin Hong; Soon-Jin Hwang; Baik-Ho Kim; Kwang-Guk An; Young-Seuk Park; Sang-Kyu Park; Han-Yong Um; Kyung-Hoon Shin (Paddy and Water Environment, 2017)

Global morphology of ionospheric F-layer scintillations using FS3/COSMIC GPS radio occultation data - Lung-Chih Tsai; Shin-Yi Su; Chao-Han Liu (GPS Solutions, 2017)

Heterologous production of a ginsenoside saponin (compound K) and its precursors in transgenic tobacco impairs the vegetative and reproductive growth - Yu Shin Gwak; Jung Yeon Han; Prakash Babu Adhikari; Chang Ho Ahn; Yong Eui Choi (Planta, 2017)

Dissipation pattern and risk quotients assessment of amisulbrom in Korean melon cultivated in plastic house conditions - Md. Humayun Kabir; A. M. Abd El-Aty; Md. Musfiqur Rahman; Hyung Suk Chung; Han Sol Lee; Sun-Hyang Park; Fazil Hacımüftüoğlu; Byung-Joon Chang; Ho-Chul Shin; Jae-Han Shim (Environmental Monitoring and Assessment, 2017)

Simulations of the Population Dynamics of Jellyfish Polyps Living on Artificial Substrates in Coastal Areas - Hong Sung Jin; Dongyeob Han; Jung-Hun Kim; Hyun-Jae Shin; Yang Ho Yoon; Chang-hoon Han (Thalassas: An International Journal of Marine Sciences, 2017)

Molecular marker analysis of Cynanchum wilfordii and C. auriculatum using the simple ARMS-PCR method with mismatched primers - Eun-Heui Han; Soo Jin Lee; Man Bae Kim; Yong-Wook Shin; Yun-Hee Kim; Shin-Woo Lee (Plant Biotechnology Reports, 2017)

Autophagic flux analysis of Arabidopsis seedlings exposed to salt stress - Hyera Jung; Jeong Hun Kim; Kwang Deok Shin; Jimi Kim; Han Nim Lee; Taijoon Chung (Journal of Plant Biology, 2017)

Helicobacter pylori infection is an independent risk factor for colonic adenomatous neoplasms - Ji Hyung Nam; Chang Won Hong; Byung Chang Kim; Aesun Shin; Kum Hei Ryu; Bum Joon Park; Bun Kim; Dae Kyung Sohn; Kyung Su Han; Jeongseon Kim; Chan Wha Lee (Cancer Causes & Control, 2017)

Biocatalytic characterization of an endo-β-1,4-mannanase produced by Paenibacillus sp. strain HY-8 - Do Young Kim; Chung Wook Chung; Han-Young Cho; Young Ha Rhee; Dong-Ha Shin; Kwang-Hee Son; Ho-Yong Park (Biotechnology Letters, 2017)

Overexpression of Telomerase Reverse Transcriptase Induces Autism-like Excitatory Phenotypes in Mice - Ki Chan Kim; Jeehae Rhee; Jong-Eun Park; Dong-Keun Lee; Chang Soon Choi; Ji-Woon Kim; Han-Woong Lee; Mi-Ryoung Song; Hee Jeong Yoo; ChiHye Chung; Chan Young Shin (Molecular Neurobiology, 2016)

Selective serotonin reuptake inhibitor sertraline inhibits voltage-dependent K+ channels in rabbit coronary arterial smooth muscle cells - Han Sol Kim; Hongliang Li; Hye Won Kim; Sung Eun Shin; Il-Whan Choi; Amy L Firth; Hyoweon Bang; Young Min Bae; Won Sun Park (Journal of Biosciences, 2016)

Temporal and spatial variations in the proximate composition, amino acid, and mineral content of Pyropia yezoensis - Sang Mok Jung; Seul Gi Kang; Ji Su Son; Jae Hyuk Jeon; Han Joo Lee; Hyun Woung Shin (Journal of Applied Phycology, 2016)

An overview on common aspects influencing the dissipation pattern of pesticides: a review - Waziha Farha; A. M. Abd El-Aty; Md. Musfiqur Rahman; Ho-Chul Shin; Jae-Han Shim (Environmental Monitoring and Assessment, 2016)

Contribution of GABRG2 Polymorphisms to Risk of Epilepsy and Febrile Seizure: a Multicenter Cohort Study and Meta-analysis - Batoul Sadat Haerian; Larry Baum; Patrick Kwan; Stacey S. Cherny; Jae-Gook Shin; Sung Eun Kim; Bok-Ghee Han; Hui Jan Tan; Azman Ali Raymond; Chong Tin Tan; Zahurin Mohamed (Molecular Neurobiology, 2016)

Various Echocardiographic Patterns of Left Ventricular Systolic Dysfunction Induced by Carbon Monoxide Intoxication - Jin-Sun Park; Kyoung-Woo Seo; Byoung-Joo Choi; So-Yeon Choi; Myeong-Ho Yoon; Gyo-Seung Hwang; Seung-Jea Tahk; Sang-Cheon Choi; Young-Gi Min; Joon-Han Shin (Cardiovascular Toxicology, 2016)

A self-contained GIM-aided Abel retrieval method to improve GNSS-Radio Occultation retrieved electron density profiles - S. Tulasi Ram; Shin-Yi Su; Lung-Chi Tsai; Chao Han Liu (GPS Solutions, 2016)

Effect of Euphorbia humifusa Willd extract on the amelioration of innate immune responses - Chang Gun Kim; Yoongho Lim; Young Han Lee; Soon Young Shin (Genes & Genomics, 2016)

Tumorigenicity Evaluation of Umbilical Cord Blood-derived Mesenchymal Stem Cells - Sang-Jin Park; Hyun-Jung Kim; Woojin Kim; Ok-Sun Kim; Sunyeong Lee; Su-Yeon Han; Eun Ju Jeong; Hyun-shin Park; Hea-Won Kim; Kyoung-Sik Moon (Toxicological Research, 2016)

Subacute Inhalation Toxicity of 3-Methylpentane - Yong Hyun Chung; Seo-Ho Shin; Jeong Hee Han; Yong-Hoon Lee (Toxicological Research, 2016)

The class III anti-arrhythmic agent, amiodarone, inhibits voltage-dependent K+ channels in rabbit coronary arterial smooth muscle cells - Hongliang Li; Han Sol Kim; Hye Won Kim; Sung Eun Shin; Won-Kyo Jung; Kwon-Soo Ha; Eun-Taek Han; Seok-Ho Hong; Amy L. Firth; Young Min Bae; Il-Whan Choi; Won Sun Park (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Holocene depositional patterns of the subaqueous Nakdong Delta on the Korea Strait with respect to sequence stratigraphy - Dong-Lim Choi; Yong-Kuk Lee; Dong-Hyeok Shin; Han-Jun Woo (Ocean Science Journal, 2016)

Development of novel tetra- and trinucleotide microsatellite markers for giant grouper Epinephelus lanceolatus using 454 pyrosequencing - Keun-Sik Kim; Choong Hwan Noh; Shin-Joo Moon; Seung-Hee Han; In-Chul Bang (Molecular Biology Reports, 2016)

A combined liquid chromatography-triple-quadrupole mass spectrometry method for the residual detection of veterinary drugs in porcine muscle, milk, and eggs - Dan Zhang; Zee-Yong Park; Jin-A Park; Seong-Kwan Kim; Daun Jeong; Sang-Hyun Cho; Jae-Han Shim; Jin-Suk Kim; A. M. Abd El-Aty; Ho-Chul Shin (Environmental Monitoring and Assessment, 2016)

Development of molecular markers, based on chloroplast and ribosomal DNA regions, to discriminate three popular medicinal plant species, Cynanchum wilfordii, Cynanchum auriculatum, and Polygonum multiflorum - Eun-Heui Han; KyeMan Cho; YoungMin Goo; ManBae Kim; Young-Wook Shin; Yun-Hee Kim; Shin-Woo Lee (Molecular Biology Reports, 2016)

Acylated neo-clerodane type diterpenoids from the aerial parts of Scutellaria coleifolia Levl. (Lamiaceae) - Shin-ichiro Kurimoto; Jian-Xin Pu; Han-Dong Sun; Hirofumi Shibata; Yoshihisa Takaishi; Yoshiki Kashiwada (Journal of Natural Medicines, 2016)

Is there a relationship between PPARD T294C/PPARGC1A Gly482Ser variations and physical endurance performance in the Korean population? - Han-Jun Jin; In-Wook Hwang; Ki-Cheol Kim; Hyun-Ik Cho; Tae-Hwan Park; Yun-A Shin; Ho-Seong Lee; Ji-Hyun Hwang; Ah-Ram Kim; Kwang-Hee Lee; Ye-Eun Shin; Ji-Yeon Lee; et al. (Genes & Genomics, 2016)

Effects of light shading and climatic conditions on the metabolic behavior of flonicamid in red bell pepper - Da-I Jung; Waziha Farha; A. M. Abd El-Aty; Sung-Woo Kim; Md. Musfiqur Rahman; Jeong-Heui Choi; Md. Humayun Kabir; So Jeong Im; Young-Jun Lee; Lieu. T. B. Truong; Ho-Chul Shin; Geon-Jae Im; et al. (Environmental Monitoring and Assessment, 2016)

Association between glutathione S-transferases M1, T1 and P1 gene polymorphisms and prostate cancer in Koreans - Ye-Eun Shin; In-Wook Hwang; Han-Jun Jin (Genes & Genomics, 2016)

MeCP2 Modulates Sex Differences in the Postsynaptic Development of the Valproate Animal Model of Autism - Ki Chan Kim; Chang Soon Choi; Ji-Woon Kim; Seol-Heui Han; Jae Hoon Cheong; Jong Hoon Ryu; Chan Young Shin (Molecular Neurobiology, 2016)

Genetic and functional characterization of an extracellular modular GH6 endo-β-1,4-glucanase from an earthworm symbiont, Cellulosimicrobium funkei HY-13 - Do Young Kim; Min Ji Lee; Han-Young Cho; Jong Suk Lee; Mi-Hwa Lee; Chung Wook Chung; Dong-Ha Shin; Young Ha Rhee; Kwang-Hee Son; Ho-Yong Park (Antonie van Leeuwenhoek, 2016)

Ca2+ clearance by plasmalemmal NCLX, Li+-permeable Na+/Ca2+ exchanger, is required for the sustained exocytosis in rat insulinoma INS-1 cells - Young-Eun Han; Shin-Young Ryu; Sun-Hyun Park; Kyu-Hee Lee; Suk-Ho Lee; Won-Kyung Ho (Pflügers Archiv - European Journal of Physiology, 2015)

Effective selection of soybean cultivars to wildfire disease pathogen Pseudomonas amygdali pv. tabaci - In Jeong Kang; Seung-Han Kim; Yong Weon Seo; Min Jeong Seo; Hyeong Kwon Shim; Dong Bum Shin; Sunggi Heu (Journal of Crop Science and Biotechnology, 2015)

Analysis of DDT and its metabolites in soil and water samples obtained in the vicinity of a closed-down factory in Bangladesh using various extraction methods - M. N. U. Al Mahmud; Farzana Khalil; Md. Musfiqur Rahman; M. I. R. Mamun; Mohammad Shoeb; A. M. Abd El-Aty; Jong-Hyouk Park; Ho-Chul Shin; Nilufar Nahar; Jae-Han Shim (Environmental Monitoring and Assessment, 2015)

Relative paleointensity data from the late Holocene deltaic sediments in Korea - Seungwon Shin; Yong-Hee Park; Jong-Hyun Park; Soojeong Han (Geosciences Journal, 2015)

A novel synthetic chalcone derivative promotes caspase-dependent apoptosis through ROS generation and activation of the UPR in MH7A cells - Jin-Hyun Kim; Yong-Joon Jeon; Jaewook Cho; Jong-Il Shin; Chae Yun Baek; Yoongho Lim; Dongsoo Koh; Soon Young Shin; Young Han Lee; Kyungho Lee (Genes & Genomics, 2015)

Expressed sequence tag analysis and annotation of genetic information from the freshwater clam, Pisidium (Neopisidium) coreanum endemic to Korea - Ji Eun Jeong; Se Won Kang; Hee-Ju Hwang; So Young Park; Bharat Bhusan Patnaik; Changmu Kim; Soonok Kim; Myung-Mo Nam; Jae Bong Lee; Tae Hun Wang; Eun Bi Park; Sun Shin Yi; et al. (Genes & Genomics, 2015)

Influence of Flaxseed Oil on Fecal Microbiota, Egg Quality and Fatty Acid Composition of Egg Yolks in Laying Hens - Jun-Yeong Lee; Sang-Kee Kang; Yun-Jeong Heo; Do-Woon Shin; Tae-Eun Park; Geon Goo Han; Gwi-Deuk Jin; Ho-Bin Lee; Eojin Jung; Hee Sung Kim; Yerim Na; Eun Bae Kim; et al. (Current Microbiology, 2015)

Ectopic expression of a hot pepper bZIP-like transcription factor in potato enhances drought tolerance without decreasing tuber yield - Seok-Jun Moon; Se-Youn Han; Dool-Yi Kim; In Sun Yoon; Dongjin Shin; Myung-Ok Byun; Hawk-Bin Kwon; Beom-Gi Kim (Plant Molecular Biology, 2015)

A Novel Compound ITC-3 Activates the Nrf2 Signaling and Provides Neuroprotection in Parkinson’s Disease Models - Ji Ae Lee; Hyo Jin Son; Ki Duk Park; Se Hee Han; Nari Shin; Ji Hyun Kim; Hye Ri Kim; Dong Jin Kim; Onyou Hwang (Neurotoxicity Research, 2015)

Cucurbitacin D induces cell cycle arrest and apoptosis by inhibiting STAT3 and NF-κB signaling in doxorubicin-resistant human breast carcinoma (MCF7/ADR) cells - Jin Mo Ku; Soon Re Kim; Se Hyang Hong; Han-Seok Choi; Hye Sook Seo; Yong Cheol Shin; Seong-Gyu Ko (Molecular and Cellular Biochemistry, 2015)

Role of the MoYAK 1 protein kinase gene in M agnaporthe oryzae development and pathogenicity - Joon‐Hee Han; Hye‐Min Lee; Jong‐Hwan Shin; Yong‐Hwan Lee; Kyoung Su Kim (Environmental Microbiology, 2015)
Summary Conidiation and appressorium differentiation are key processes for polycyclic dissemination and infection in many pathogens. Our previous study using DNA microarray led to the discovery of the MoYAK 1 gene in M agnaporthe oryzae that is orthologous to YAK 1 in S accharomyces cerevisiae . Although the mechanistic roles of YAK 1 in S . cerevisiae have been described, roles of MoYAK 1 in M . oryzae , a phytopathogenic fungus responsible for rice blast, remain uncharacterized. Targeted disruption of MoYAK 1 results in pleiotropic defects in M . oryzae development and pathogenicity. The Δ M oyak1 mutant exhibits a severe reduction in aerial hyphal formation and conidiation. Conidia in the Δ M oyak1 are delayed in germination and demonstrate decreased glycogen content in a conidial age‐dependent manner. The expression of hydrophobin‐coding genes is dramatically changed in the Δ M oyak1 mutant, leading to a loss of surface hydrophobicity. Unlike the complete inability of the Δ M oyak1 mutant to develop appressoria on an inductive surface, the mutant forms appressoria of abnormal morphology in response to exogenous cyclic adenosine‐5′‐monophosphate and host‐driven signals, which are all defective in penetrating host tissues due to abnormalities in glycogen and lipid metabolism, turgor generation and cell wall integrity. These data indicate that MoYAK 1 is a protein kinase important for the development and pathogenicity of M . oryzae .

A transcriptomic analysis of the response of the arctic pteropod Limacina helicina to carbon dioxide-driven seawater acidification - Hye Yeon Koh; Jun Hyuck Lee; Se Jong Han; Hyun Park; Seung Chul Shin; Sung Gu Lee (Polar Biology, 2015)

Pharmacokinetic scaling of epirubicin using allometric and species-invariant time methods - Dae Hwan Shin; Seung Hyeok Park; Sung Woo Jeong; Oh-Seung Kwon; Chun-Woong Park; Kun Han; Youn Bok Chung (Journal of Pharmaceutical Investigation, 2015)

Modulation of Pharmacokinetic and Cytotoxicity Profile of Imatinib Base by Employing Optimized Nanostructured Lipid Carriers - Biki Gupta; Bijay Kumar Poudel; Tuan Hiep Tran; Roshan Pradhan; Hyuk-Jun Cho; Jee-Heon Jeong; Beom Soo Shin; Han-Gon Choi; Chul Soon Yong; Jong Oh Kim (Pharmaceutical Research, 2015)

Cold adaptation of a psychrophilic chaperonin from Psychrobacter sp. and its application for heterologous protein expression - Han-Woo Kim; Ah Ram Wi; Byoung Wook Jeon; Jun Hyuck Lee; Seung Chul Shin; Hyun Park; Sung-Jong Jeon (Biotechnology Letters, 2015)

Podocyte hypertrophy precedes apoptosis under experimental diabetic conditions - Sun Ha Lee; Sung Jin Moon; Jisun Paeng; Hye-Young Kang; Bo Young Nam; Seonghun Kim; Chan Ho Kim; Mi Jung Lee; Hyung Jung Oh; Jung Tak Park; Seung Hyeok Han; Tae-Hyun Yoo; et al. (Apoptosis, 2015)

Sanitizing Effect of Ethanol Against Biofilms Formed by Three Gram-Negative Pathogenic Bacteria - Han-Saem Park; Youngseok Ham; Keum Shin; Yeong-Suk Kim; Tae-Jong Kim (Current Microbiology, 2015)

Predisposing roles of paraoxonase-1 genetic variants in Korean ischemic stroke patients - Yunkyung Cho; Jung Oh Kim; Young Joo Jeon; Gun Ho Choi; Jee Soo Shin; Sung Hwan Cho; Seung Hun Oh; In Bo Han; Byoung Soo Shin; Ok Joon Kim; Nam Keun Kim (Genes & Genomics, 2015)

Size-dependent clearance of gold nanoparticles from lungs of Sprague–Dawley rats after short-term inhalation exposure - Sung Gu Han; Jong Seong Lee; Kangho Ahn; Yong Soon Kim; Jin Kwon Kim; Ji Huyn Lee; Jae Hoon Shin; Ki Soo Jeon; Wan Seob Cho; Nam Woong Song; Mary Gulumian; Beom Soo Shin; et al. (Archives of Toxicology, 2015)

Depressive-Like Behaviors in a Rat Model of Chronic Cerebral Hypoperfusion - Sang Rim Lee; Boryoung Choi; Saswati Paul; Ju-Ha Seo; Dong Bin Back; Jung-Soo Han; Dong-Hee Choi; Kyoung Ja Kwon; Chan Young Shin; Jongmin Lee; Seol-Heui Han; Hahn Young Kim (Translational Stroke Research, 2015)

Bioactive injectables based on calcium phosphates for hard tissues: A recent update - Roman A. Perez; Song-Hee Shin; Cheol-Min Han; Hae-Won Kim (Tissue Engineering and Regenerative Medicine, 2015)

The influences of CYP2D6 genotypes and drug interactions on the pharmacokinetics of venlafaxine: exploring predictive biomarkers for treatment outcomes - Fen Jiang; Hae-Deun Kim; Han-Sung Na; Seok-Yong Lee; Doo-Won Seo; Jong-Yeol Choi; Ji-Hye Ha; Hee-Jung Shin; Young-Hoon Kim; Myeon-Woo Chung (Psychopharmacology, 2015)

Polypeptide-based Micelles for Delivery of Irinotecan: Physicochemical and In vivo Characterization - Thiruganesh Ramasamy; Ju Yeon Choi; Hyuk Jun Cho; Subbaih Kandasamy Umadevi; Beom Soo Shin; Han-Gon Choi; Chul Soon Yong; Jong Oh Kim (Pharmaceutical Research, 2015)

Phospholipase D1 Increases Bcl-2 Expression During Neuronal Differentiation of Rat Neural Stem Cells - Shin-Young Park; Weina Ma; Sung Nyo Yoon; Min Jeong Kang; Joong-Soo Han (Molecular Neurobiology, 2015)

Roles of Tsp66E and Tsp74F in border cell migration and the maintenance of border cell adhesion in Drosophila - Haemin Jeong; Seung Yeop Han; Minjung Lee; Soojin Lee; Myeongcheol Shin; Youngjae Jeon; Kyungho Lee; Kyoung Sang Cho (Genes & Genomics, 2015)

Identification of key factors influencing primary productivity in two river-type reservoirs by using principal component regression analysis - Yeonjung Lee; Sun-Yong Ha; Hae-Kyung Park; Myung-Soo Han; Kyung-Hoon Shin (Environmental Monitoring and Assessment, 2015)

Effects of the algicide, thiazolidinedione derivative TD49, on microbial communities in a mesocosm experiment - Moonho Son; Seung Ho Baek; Kyoungsoon Shin; Keun-Hyung Choi; Si Wouk Kim; Jaewon Ryu; Hoon Cho; Seung Won Jung; Ik Kyo Chung; Young-Ok Kim; Myung-Soo Han (Environmental Monitoring and Assessment, 2015)

Direct sequencing for comprehensive screening of LDLR genetic polymorphisms among five ethnic populations - Jeong-Hyun Kim; Hyun Sub Cheong; Lyoung Hyo Kim; Hee Jung Shin; Han Sung Na; Myeon Woo Chung; Hyoung Doo Shin (Genes & Genomics, 2015)

The effect of composite graft with deproteinized bovine bone mineral and mineralized solvent-dehydrated bone on exophytic bone formation in rabbit calvarial model - Hwa-Suk Seok; Yeek Herr; Jong-Hyuk Chung; Seung-Il Shin; Ji-Young Han; Seung-Yun Shin (Tissue Engineering and Regenerative Medicine, 2014)

Genome-wide analyses of DNA-binding proteins harboring AT-hook motifs and their functional roles in the rice blast pathogen, Magnaporthe oryzae - Jong-Hwan Shin; Joon-Hee Han; Kyoung Su Kim (Genes & Genomics, 2014)

Induction of immune responses in mice and pigs by oral administration of classical swine fever virus E2 protein expressed in rice calli - Myunghwan Jung; Yun Ji Shin; Ju Kim; Seung-Bin Cha; Won-Jung Lee; Min-Kyoung Shin; Seung Won Shin; Moon-Sik Yang; Yong-Suk Jang; Tae-Ho Kwon; Han Sang Yoo (Archives of Virology, 2014)

Enhanced glycogen synthase kinase-3β activity mediates podocyte apoptosis under diabetic conditions - Jisun Paeng; Jae Hyun Chang; Sun Ha Lee; Bo Young Nam; Hye-Young Kang; Seonghun Kim; Hyung Jung Oh; Jung Tak Park; Seung Hyeok Han; Tae-Hyun Yoo; Shin-Wook Kang (Apoptosis, 2014)

Large-scale screening of rice accessions to evaluate resistance to bakanae disease - Myung-Hee Kim; Yeon-Jae Hur; Saes Beul Lee; Tackmin Kwon; Un-Ha Hwang; Soo-Kwon Park; Young-Nam Yoon; Jong-Hee Lee; Jun-Hyeon Cho; Dongjin Shin; Tae Heon Kim; Sang-Ik Han; et al. (Journal of General Plant Pathology, 2014)

Development of Vorinostat-Loaded Solid Lipid Nanoparticles to Enhance Pharmacokinetics and Efficacy against Multidrug-Resistant Cancer Cells - Tuan Hiep Tran; Thiruganesh Ramasamy; Duy Hieu Truong; Beom Soo Shin; Han-Gon Choi; Chul Soon Yong; Jong Oh Kim (Pharmaceutical Research, 2014)

Complete genome sequence of the Pectobacterium carotovorum subsp. carotovorum virulent bacteriophage PM1 - Jeong-A Lim; Hakdong Shin; Dong Hwan Lee; Sang-Wook Han; Ju-Hoon Lee; Sangryeol Ryu; Sunggi Heu (Archives of Virology, 2014)

Ectopic expression of CaWRKY1, a pepper transcription factor, enhances drought tolerance in transgenic potato plants - Seok-Jun Moon; Se-Youn Han; Dool-Yi Kim; Beom-Gi Kim; In Sun Yoon; Dongjin Shin; Hawk-Bin Kwon; Myung-Ok Byun (Journal of Plant Biology, 2014)

Large genomic rearrangement of BRCA1 and BRCA2 genes in familial breast cancer patients in Korea - Ja Young Cho; Dae-Yeon Cho; Sei Hyun Ahn; Su-Youn Choi; Inkyung Shin; Hyun Gyu Park; Jong Won Lee; Hee Jeong Kim; Jong Han Yu; Beom Seok Ko; Bo Kyung Ku; Byung Ho Son (Familial Cancer, 2014)

The effect of LED light spectra on antioxidant system by thermal stress in goldfish, Carassius auratus - Na Na Kim; Young Jae Choi; Hyun Suk Shin; Jee Rey Lim; Jeong Min Han; Ji Hyung Cho; Jehee Lee; Gyung-Suk Kil; Cheol Young Choi (Molecular & Cellular Toxicology, 2014)

tPA Regulates Neurite Outgrowth by Phosphorylation of LRP5/6 in Neural Progenitor Cells - Sung Hoon Lee; Hyun Myung Ko; Kyoung Ja Kwon; Jongmin Lee; Seol-Heui Han; Dong Wook Han; Jae Hoon Cheong; Jong Hoon Ryu; Chan Young Shin (Molecular Neurobiology, 2014)

Targeting Estrogen Receptors for the Treatment of Alzheimer’s Disease - Jung Hoon Lee; Yanxialei Jiang; Dong Hoon Han; Seung Kyun Shin; Won Hoon Choi; Min Jae Lee (Molecular Neurobiology, 2014)

Class 3 inhibition of hERG K+ channel by caffeic acid phenethyl ester (CAPE) and curcumin - Seong Woo Choi; Kyung Su Kim; Dong Hoon Shin; Hae Young Yoo; Han Choe; Tae Hee Ko; Jae Boum Youm; Woo Kyung Kim; Yin Hua Zhang; Sung Joon Kim (Pflügers Archiv - European Journal of Physiology, 2013)

Delphinidin prevents hypoxia-induced mouse embryonic stem cell apoptosis through reduction of intracellular reactive oxygen species-mediated activation of JNK and NF-κB, and Akt inhibition - Bit Na Seo; Jung Min Ryu; Seung Pil Yun; Ji Hoon Jeon; Su Shin Park; Keon Bong Oh; Jin-Ki Park; Ho Jae Han (Apoptosis, 2013)

Validation of high-performance liqid chromatography method to determine epirubicin and its pharmacokinetics after intravenous bolus administration in rats - Dae Hwan Shin; Seong Hyeok Park; Oh-Seung Kwon; Chun-Woong Park; Kun Han; Youn Bok Chung (Journal of Pharmaceutical Investigation, 2013)

A novel method using an acedan-based Zn(DPA) probe to monitor ATP localization in an in vivo system - Seo Jin Lee; Alla Sreenivasa Rao; Youn Ho Shin; Hyung-Joo Chung; Youngbuhm Huh; Kyo Han Ahn; Junyang Jung (Journal of Molecular Histology, 2013)

Analysis of mRNA expression profiles highlights alterations in modulation of the DNA damage-related genes under butanal exposure in A549 human alveolar epithelial cells - Hyo-Sun Lee; Mi-Kyung Song; Han-Seam Choi; Chan-Young Shin; Eun-Il Lee; Jae-Chun Ryu (Molecular & Cellular Toxicology, 2013)

Distribution of adipocyte-related cells in skeletal muscle of rainbow trout Oncorhynchus mykiss - Yuna Han; Gen Kaneko; Reiko Nagasaka; Hidehiro Kondo; Ikuo Hirono; Shin-Ichiro Takahashi; Shugo Watabe; Hideki Ushio (Fisheries Science, 2013)

Prediction of the tacrolimus population pharmacokinetic parameters according to CYP3A5 genotype and clinical factors using NONMEM in adult kidney transplant recipients - Nayoung Han; Hwi-yeol Yun; Jin-yi Hong; In-Wha Kim; Eunhee Ji; Su Hyun Hong; Yon Su Kim; Jongwon Ha; Wan Gyoon Shin; Jung Mi Oh (European Journal of Clinical Pharmacology, 2013)

Erratum to: Overexpression of phytochrome A and its hyperactive mutant improves shade tolerance and turf quality in creeping bentgrass and zoysiagrass - Markkandan Ganesan; Yun-Jeong Han; Tae-Woong Bae; Ok-Jin Hwang; Thummala Chandrasekhar; Ah-Young Shin; Chang-Hyo Goh; Satoshi Nishiguchi; In-Ja Song; Hyo-Yeon Lee; Jeong-Il Kim; Pill-Soon Song (Planta, 2012)

Overexpression of phytochrome A and its hyperactive mutant improves shade tolerance and turf quality in creeping bentgrass and zoysiagrass - Markkandan Ganesan; Yun-Jeong Han; Tae-Woong Bae; Ok-Jin Hwang; Thummala Chandrasekkhar; Ah-Young Shin; Chang-Hyo Goh; Satoshi Nishiguchi; In-Ja Song; Hyo-Yeon Lee; Jeong-Il Kim; Pill-Soon Song (Planta, 2012)

AMPK activation reduces vascular permeability and airway inflammation by regulating HIF/VEGFA pathway in a murine model of toluene diisocyanate-induced asthma - Seoung Ju Park; Kyung Sun Lee; So Ri Kim; Han Jung Chae; Wan Hee Yoo; Dong Im Kim; Myoung Shin Jeon; Yong Chul Lee (Inflammation Research, 2012)

Overexpression of an Arabidopsis β-glucosidase gene enhances drought resistance with dwarf phenotype in creeping bentgrass - Yun-Jeong Han; Kyu-Chang Cho; Ok-Jin Hwang; Yun-Sung Choi; Ah-Young Shin; Inhwan Hwang; Jeong-Il Kim (Plant Cell Reports, 2012)

Erratum to: Apigenin induces apoptosis via extrinsic pathway, inducing p53 and inhibiting STAT3 and NFκB signaling in HER2-overexpressing breast cancer cells - Hye-Sook Seo; Han-Seok Choi; Soon-Re Kim; Youn Kyung Choi; Sang-Mi Woo; Incheol Shin; Jong-Kyu Woo; Sang-Yoon Park; Yong Cheol Shin; Seong-Gyu Ko (Molecular and Cellular Biochemistry, 2012)

Insects perceive local sex ratio in the absence of tactile or visual sex-specific cues - Chang S. Han; Chang-Ku Kang; Hong-Sup Shin; Jeong-Hyun Lee; Mi-Rye Bae; Sang-Im Lee; Piotr G. Jablonski (Behavioral Ecology and Sociobiology, 2012)

Porcine SPP1 gene polymorphism association with phenotypic traits in the Landrace × Jeju (Korea) black pig F2 population - Sang-Hyun Han; Kwang-Yun Shin; Sung-Soo Lee; Moon-Suck Ko; Hong-Shik Oh; In-Cheol Cho (Molecular Biology Reports, 2012)

Apigenin induces apoptosis via extrinsic pathway, inducing p53 and inhibiting STAT3 and NFκB signaling in HER2-overexpressing breast cancer cells - Hye-Sook Seo; Han-Seok Choi; Soon-Re Kim; Youn Kyung Choi; Sang-Mi Woo; Incheol Shin; Jong-Kyu Woo; Sang-Yoon Park; Yong Cheol Shin; Seong-Kyu Ko (Molecular and Cellular Biochemistry, 2012)

BMP4 signaling mediates Zeb family in developing mouse tooth - Jeong-Oh Shin; Eun-Jung Kim; Kyoung-Won Cho; Eizo Nakagawa; Hyuk-Jae Kwon; Sung-Won Cho; Han-Sung Jung (Histochemistry and Cell Biology, 2012)

Identification of genes induced by dibutyl phthalate in human thyroid follicular FTC-238 cells - Mee Song; Mi-Kyung Song; Han-Seam Choi; Ji-Seong Yoon; Chan-Young Shin; Hae-Yeon Choi; Youn-Jung Kim; Jae-Chun Ryu (Toxicology and Environmental Health Sciences, 2012)

Prevalence and genetic characterization of respiratory syncytial virus (RSV) in hospitalized children in Korea - Yun Hee Baek; Eun Hye Choi; Min-Suk Song; Philippe Noriel Q. Pascua; Hyeok-il Kwon; Su-Jin Park; Jun Han Lee; Sung-Il Woo; Byung-Hoon Ahn; Heon-Seok Han; Yoon-Soo Hahn; Kyeong-Seob Shin; et al. (Archives of Virology, 2012)

Clinical and genetic factors affecting tacrolimus trough levels and drug-related outcomes in Korean kidney transplant recipients - In-Wha Kim; Yoo Jin Moon; Eunhee Ji; Kyung Im Kim; Nayoung Han; Sung Ju Kim; Wan Gyoon Shin; Jongwon Ha; Jeong-Hyun Yoon; Hye Suk Lee; Jung Mi Oh (European Journal of Clinical Pharmacology, 2012)

Isolation and Characterization of a Lytic Myoviridae Bacteriophage PAS-1 with Broad Infectivity in Aeromonas salmonicida - J. H. Kim; J. S. Son; Y. J. Choi; C. H. Choresca; S. P. Shin; J. E. Han; J. W. Jun; D. H. Kang; C. Oh; S. J. Heo; S. C. Park (Current Microbiology, 2012)

Association of colorectal adenoma with components of metabolic syndrome - Byung Chang Kim; Aesun Shin; Chang Won Hong; Dae Kyung Sohn; Kyung Su Han; Kum Hei Ryu; Bum Joon Park; Ji Hyung Nam; Ji Won Park; Hee Jin Chang; Hyo Seong Choi; Jeongseon Kim; et al. (Cancer Causes & Control, 2012)

Identification of a C2H2-type zinc finger transcription factor (ZAT10) from Arabidopsis as a substrate of MAP kinase - Xuan Canh Nguyen; Sun Ho Kim; Kyunghee Lee; Kyung Eun Kim; Xiao-Min Liu; Hay Ju Han; My Hanh Thi Hoang; Shin-Woo Lee; Jong Chan Hong; Yong-Hwan Moon; Woo Sik Chung (Plant Cell Reports, 2012)

Induction of Fas-mediated extrinsic apoptosis, p21WAF1-related G2/M cell cycle arrest and ROS generation by costunolide in estrogen receptor-negative breast cancer cells, MDA-MB-231 - Youn Kyung Choi; Hye Sook Seo; Han Seok Choi; Hyeong Sim Choi; Soon Re Kim; Yong Cheol Shin; Seong-Gyu Ko (Molecular and Cellular Biochemistry, 2012)

miR-200b regulates cell migration via Zeb family during mouse palate development - Jeong-Oh Shin; Eizo Nakagawa; Eun-Jung Kim; Kyoung-Won Cho; Jong-Min Lee; Sung-Won Cho; Han-Sung Jung (Histochemistry and Cell Biology, 2012)

The novel function of Oct3/4 in mouse tooth development - Eizo Nakagawa; Li Zhang; Eun-Jung Kim; Jeong-Oh Shin; Sung-Won Cho; Hayato Ohshima; Han-Sung Jung (Histochemistry and Cell Biology, 2012)

Gene expression analysis identifies DNA damage-related markers of benzo[a]pyrene exposure in HepG2 human hepatocytes - Mi-Kyung Song; Ji-Seong Yoon; Mee Song; Han-Seam Choi; Chan-Young Shin; Youn-Jung Kim; Woo-In Ryu; Hyo-Sun Lee; Jae-Chun Ryu (Toxicology and Environmental Health Sciences, 2012)

Determination of three preservatives, cresol, chlorocresol and benzethonium, in drugs by high performance liquid chromatography–ultraviolet (HPLC–UV) detection - Jin Gyun Lee; Sang-yeon Shin; Hae-jin Shin; Yoonyoung Huh; Seul Ji Lee; Dong-Hwan Kim; Sujung Lee; Young-Ok Kim; Sang Beom Han; Jeongmi Lee; Jeong Hill Park; Sung Won Kwon (Journal of Pharmaceutical Investigation, 2012)

The novel expression of Oct3/4 and Bmi1 in the root development of mouse molars - Eizo Nakagawa; Li Zhang; Jeong-Oh Shin; Eun-Jung Kim; Sung-Won Cho; Hayato Ohshima; Zhi Chen; Han-Sung Jung (Cell and Tissue Research, 2012)

Complete genomic sequence of a T4-like bacteriophage, phiAS4, infecting Aeromonas salmonicida subsp. salmonicida - J. H. Kim; J. S. Son; Y. J. Choi; C. H. Choresca; S. P. Shin; J. E. Han; J. W. Jun; S. C. Park (Archives of Virology, 2012)

Genomic sequence of infectious hypodermal and hematopoietic necrosis virus (IHHNV) KLV-2010-01 originating from the first Korean outbreak in cultured Litopenaeus vannamei - J. H. Kim; H. K. Kim; V. G. Nguyen; B. K. Park; C. H. Choresca; S. P. Shin; J. E. Han; J. W. Jun; S. C. Park (Archives of Virology, 2012)

MiR-200b is involved in Tgf-β signaling to regulate mammalian palate development - Jeong-Oh Shin; Jong-Min Lee; Kyoung-Won Cho; Sungwook Kwak; Hyuk-Jae Kwon; Min-Jung Lee; Sung-Won Cho; Kye-Seong Kim; Han-Sung Jung (Histochemistry and Cell Biology, 2012)

The MCP-1/CCR2 axis in podocytes is involved in apoptosis induced by diabetic conditions - Bo Young Nam; Jisun Paeng; Seung Hye Kim; Sun Ha Lee; Do Hee Kim; Hye-Young Kang; Jin Ji Li; Seung-Jae Kwak; Jung Tak Park; Tae-Hyun Yoo; Seung Hyeok Han; Dong Ki Kim; et al. (Apoptosis, 2012)

Comparative analysis of expressed sequence tags (ESTs) between normal group and softness syndrome group in Halocynthia roretzi - Ji Eun Jeong; Se Won Kang; Yun Kyung Shin; Je Cheon Jun; Young-Ok Kim; Young Baek Hur; Jae-Hyung Kim; Sung-Hwa Chae; Jun-Sang Lee; In ho Choi; Yeon Soo Han; Dae-Hyun Seog; et al. (Molecular & Cellular Toxicology, 2011)

Validation of international reference ionosphere models using in situ measurements from GRACE K-band ranging system and CHAMP planar Langmuir probe - Choon-Ki Lee; Shin-Chan Han; Dieter Bilitza; Jong-Kyun Chung (Journal of Geodesy, 2011)

Renal ischemia–reperfusion injury causes intercalated cell-specific disruption of occludin in the collecting duct - Su-Youn Lee; Jung-A Shin; H. Moo Kwon; I. David Weiner; Ki-Hwan Han (Histochemistry and Cell Biology, 2011)

Shh signaling is essential for rugae morphogenesis in mice - Jong-Min Lee; Seita Miyazawa; Jeong-Oh Shin; Hyuk-Jae Kwon; Dae-Woon Kang; Byung-Jai Choi; Jae-Ho Lee; Shigeru Kondo; Sung-Won Cho; Han-Sung Jung (Histochemistry and Cell Biology, 2011)

Expression of myeloperoxidase in swine influenza virus (SIV)-infected neutrophils in lungs from pigs experimentally infected with SIV subtype H1N2 - Bongtae Kim; Jeoung Hwa Shin; Kiwon Han; Hwi Won Seo; Yeonsu Oh; Ikjae Kang; Changhoon Park; Bog-Hieu Lee; Jin Sil Jang; Sung-Hoon Kim; Chanhee Chae (Veterinary Research Communications, 2011)

Human chorionic-plate-derived mesenchymal stem cells and Wharton’s jelly-derived mesenchymal stem cells: a comparative analysis of their potential as placenta-derived stem cells - Mi Jeong Kim; Kyung Seon Shin; Jin Hee Jeon; Dong Ryul Lee; Sung Han Shim; Jin Kyeoung Kim; Dong-Hyun Cha; Tae Ki Yoon; Gi Jin Kim (Cell and Tissue Research, 2011)

Prevalence and different characteristics of two serotypes of Streptococcus parauberis isolated from the farmed olive flounder, Paralichthys olivaceus (Temminck and Schlegel), in Korea - S Y Han; B K Kang; B J Kang; S P Shin; B H Soen; J M Kim; J H Kim; C H Choresca; J E Han; J W Jun; S C Park (Journal of Fish Diseases, 2011)
The prevalence of two serotypes of Streptococcus parauberis isolated from the olive flounder, Paralichthys olivaceus , was evaluated in a total of 29 isolates between 2003 and 2010 in Korea. Streptococcus parauberis isolates were divided into two serologically distinct types (serotype 1 and serotype 2), except for one strain (S1091), using an agglutination assay with rabbit antiserum, and serotype 1 was identified as the dominant type (24 of 29 isolates) in this study. To identify the characteristics of the two serotypes of S. parauberis , we conducted a biochemical test using the API 20 Strep kit, a transmission electron microscopy (TEM) assay, sequence analysis of 16S‐23S rRNA intergenic spacer region (ISR) and a pathogenicity test. In TEM, both serotypes possessed polysaccharide capsule layers around the cell surface when bacterial cells were treated with a homologous serotype of rabbit antiserum. However, we were unable to discriminate serotype‐specific biochemical characteristics and genetic characteristics of 16S‐23S rRNA ISR between the two serotypes. In the pathogenicity test, the serotype 1 strains induced significantly higher mortality than the serotype 2 strains in olive flounder when experimentally inoculated via the intraperitoneal route.

Wnt5a plays a crucial role in determining tooth size during murine tooth development - Jinglei Cai; Noriko Mutoh; Jeong-Oh Shin; Nobuyuki Tani-Ishii; Hayato Ohshima; Sung-Won Cho; Han-Sung Jung (Cell and Tissue Research, 2011)

Synthesis of an integrated biorefinery via the C–H–O ternary diagram - Douglas Han Shin Tay; Denny Kok Sum Ng; Houssein Kheireddine; Mahmoud M. El-Halwagi (Clean Technologies and Environmental Policy, 2011)

Reciprocal interactions of Fgf10/Fgfr2b modulate the mouse tongue epithelial differentiation - Wern-Joo Sohn; Hye-In Jung; Min-A Choi; Jin-Hyun Han; Gi-Jeong Gwon; Hitoshi Yamamoto; Sanggyu Lee; Zae Young Ryoo; Eui-Kyun Park; Hong-In Shin; Han-Sung Jung; Jae-Young Kim (Cell and Tissue Research, 2011)

Molecular phylogenetic assessment of the genus Hyphodiscus with description of Hyphodiscus hyaloscyphoides sp. nov. - Tsuyoshi Hosoya; Jae-Gu Han; Gi-Ho Sung; Yumiko Hirayama; Kazuaki Tanaka; Kentaro Hosaka; Isshin Tanaka; Hyeon-Dong Shin (Mycological Progress, 2011)

A genome-wide association analysis reveals 1p31 and 2p13.3 as susceptibility loci for Kawasaki disease - Jae-Jung Kim; Young Mi Hong; Saejung Sohn; Gi Young Jang; Kee-Soo Ha; Sin Weon Yun; Myung Ki Han; Kyung-Yil Lee; Min Seob Song; Hyoung Doo Lee; Dong Soo Kim; Jong-Eun Lee; et al. (Human Genetics, 2011)

Importance of region-specific epithelial rearrangements in mouse rugae development - Wern-Joo Sohn; Hitoshi Yamamoto; Hong-In Shin; Zae Young Ryoo; Sanggyu Lee; Yong-Chul Bae; Han-Sung Jung; Jae-Young Kim (Cell and Tissue Research, 2011)

Local kallikrein–kinin system is involved in podocyte apoptosis under diabetic conditions - Seung-Jae Kwak; Jisun Paeng; Do Hee Kim; Sun Ha Lee; Bo-Young Nam; Hye Young Kang; Jin Ji Li; Dong-Sub Jung; Seung Hyeok Han; Dong-Ryeol Ryu; Jung Tak Park; Tae Ik Chang; et al. (Apoptosis, 2011)

Trichome density of main stem is tightly linked to PepMoV resistance in chili pepper (Capsicum annuum L.) - Hyun Jung Kim; Jung-Heon Han; Seungill Kim; Heung Ryul Lee; Jun-Sung Shin; Jeong-Ho Kim; Juok Cho; Young Ho Kim; Hee Jae Lee; Byung-Dong Kim; Doil Choi (Theoretical and Applied Genetics, 2011)

Determination of Field-Incurred Chlorfluazuron Residues in the Peach - Jeong-Heui Choi; Md. Iqbal Rouf Mamun; Jong-Hyouk Park; Eun-Ho Shin; Jae-Han Shim (Bulletin of Environmental Contamination and Toxicology, 2011)

One centimeter-level observations of diurnal ocean tides from global monthly mean time-variable gravity fields - Shin-Chan Han; Richard D. Ray; Scott B. Luthcke (Journal of Geodesy, 2010)

Methylation patterns of genes coding for drug-metabolizing enzymes in tamoxifen-resistant breast cancer tissues - Sun Jung Kim; Han-Sung Kang; So-Youn Jung; Sun Young Min; Seeyoun Lee; Seok Won Kim; Youngmee Kwon; Keun Seok Lee; Kyung Hwan Shin; Jungsil Ro (Journal of Molecular Medicine, 2010)

Antitumor and antimetastatic effects of licochalcone A in mouse models - Jin-Kyung Kim; Eun Kyung Shin; Jun Hong Park; Yoon Hee Kim; Jung Han Yoon Park (Journal of Molecular Medicine, 2010)

Amelioration of hyperglycemia by intestinal overexpression of glucagon-like peptide-1 in mice - Meng-Ju Liu; Jaeseok Han; Young-Sun Lee; Mi-Sung Park; Seungjin Shin; Hee-Sook Jun (Journal of Molecular Medicine, 2010)

Oligometastases confined one organ from colorectal cancer treated by SBRT - Jin-Kyu Kang; Mi-Sook Kim; Jin Ho Kim; Seong Yul Yoo; Chul Koo Cho; Kwang Mo Yang; Hyung Jun Yoo; Young Seok Seo; Dong Han Lee; Hae Jin Kang; Young Han Kim; Ui-Sup Shin (Clinical & Experimental Metastasis, 2010)

Control of Algal Scum Using Top-Down Biomanipulation Approaches and Ecosystem Health Assessments for Efficient Reservoir Management - Kwang-Guk An; Jae-Yon Lee; Hema K. Kumar; Sang-Jae Lee; Soon-Jin Hwang; Baik-Ho Kim; Young-Seuk Park; Kyung-Hoon Shin; Sangkyu Park; Han-Yong Um (Water, Air, & Soil Pollution, 2010)

SINE indel polymorphism of AGL gene and association with growth and carcass traits in Landrace × Jeju black pig F2 population - Sang-Hyun Han; Kwang-Yun Shin; Sung-Soo Lee; Moon-Suck Ko; Dong Kee Jeong; Hong-Shik Oh; Byoung-Chul Yang; In-Cheol Cho (Molecular Biology Reports, 2010)

Antibacterial activity of novel naphthoquiones derivatives - Yongseog Chung; Ren shu Quan; Hyeon Mo Chang; Soo Han Kwon; Soon-Ja Kim; Young-Sam Im; Kyeong Seob Shin; Kyung-Do Park; Hak-Kyo Lee; Joong-Kook Choi (Genes & Genomics, 2009)

Luminescent Donor-Acceptor β-Diketones: Modulation of Emission by Solvent Polarity and Group II Metal Binding - Guoqing Zhang; Shin Han Kim; Ruffin E. Evans; Byeong Hyo Kim; J. N. Demas; Cassandra L. Fraser (Journal of Fluorescence, 2009)

Analysis of genetic diversity and population structure of rice cultivars from Korea, China and Japan using SSR markers - Weiguo Zhao; Jong-Wook Chung; Kyung-Ho Ma; Tae-San Kim; Seung-Min Kim; Dong-Il Shin; Chang-Ho Kim; Han-Mo Koo; Yong-Jin Park (Genes & Genomics, 2009)

Chloroplast-targeted expression of synthetic cry1Ac in transgenic rice as an alternative strategy for increased pest protection - Eun Hye Kim; Seok Cheol Suh; Beom Seok Park; Kong Sik Shin; Soon Jong Kweon; Eun Jung Han; Su-Hyun Park; Youn Shic Kim; Ju-Kon Kim (Planta, 2009)

Changes in anthocyanin and isoflavone concentrations in black seed-coated soybean at different planting locations - Tae Joung Ha; Jin Hwan Lee; Sang-Ouk Shin; Seong-Hyu Shin; Sang-Ik Han; Hyun-Tae Kim; Jong-Min Ko; Myong-Hee Lee; Keum-Yong Park (Journal of Crop Science and Biotechnology, 2009)

Novel Approach of Predicting Fracture Load in the Human Proximal Femur Using Non-Invasive QCT Imaging Technique - Taeyong Lee; Barry P. Pereira; Yoon-Sok Chung; Han Jin Oh; Jae Bong Choi; Dohyung Lim; Jun Hwan Shin (Annals of Biomedical Engineering, 2009)

Overexpression of lipid transfer protein (LTP) genes enhances resistance to plant pathogens and LTP functions in long-distance systemic signaling in tobacco - Sujon Sarowar; Young Jin Kim; Ki Deok Kim; Byung Kook Hwang; Sung Han Ok; Jeong Sheop Shin (Plant Cell Reports, 2009)

Introducing pulsed low-intensity ultrasound to culturing human umbilical cord-derived mesenchymal stem cells - Jong Hyun Yoon; Eun Youn Roh; Sue Shin; Nam Hee Jung; Eun Young Song; Dong Soon Lee; Kyou Sup Han; Joung Sung Kim; Byoung Jae Kim; Hye Won Jeon; Kang Sup Yoon (Biotechnology Letters, 2009)

Transgenic peppers that are highly tolerant to a new CMV pathotype - Yun Hee Lee; Min Jung; Sun Hee Shin; Ji Hee Lee; Soon Ho Choi; Nam Han Her; Jang Ha Lee; Ki Hyun Ryu; Kee Yoeup Paek; Chee Hark Harn (Plant Cell Reports, 2009)

Reduced sulfur compounds in ambient air surrounding an industrial region in Korea - Raktim Pal; Ki-Hyun Kim; Eui-Chan Jeon; Sang-Keun Song; Zang-Ho Shon; Shin-Young Park; Ki-Han Lee; Sun-Jin Hwang; Jong-Min Oh; Youn-Seo Koo (Environmental Monitoring and Assessment, 2009)

Adaptive response to GSH depletion and resistance to l-buthionine-(S,R)-sulfoximine: involvement of Nrf2 activation - Hyang-Rim Lee; Jeong-Min Cho; Dong-ha Shin; Chul Soon Yong; Han-Gon Choi; Nobunao Wakabayashi; Mi-Kyoung Kwak (Molecular and Cellular Biochemistry, 2008)

Licochalcone A isolated from licorice suppresses lipopolysaccharide-stimulated inflammatory reactions in RAW264.7 cells and endotoxin shock in mice - Hyuck-Se Kwon; Jun Hong Park; Dae Hwan Kim; Yoon Hee Kim; Jung Han Yoon Park; Hyun-Kyung Shin; Jin-Kyung Kim (Journal of Molecular Medicine, 2008)

Abundance and pigment type composition of picocyanobacteria in Barguzin Bay, Lake Baikal - Toshiya Katano; Shin-ichi Nakano; Osamu Mitamura; Haruko Yoshida; Hisayuki Azumi; Yoshiki Matsuura; Yuji Tanaka; Hiraku Maezono; Yasuhiro Satoh; Takeshi Satoh; Yuko Sugiyama; Yasunori Watanabe; et al. (Limnology, 2008)

Localized spectral analysis of global satellite gravity fields for recovering time-variable mass redistributions - Shin-Chan Han; Pavel Ditmar (Journal of Geodesy, 2008)

Glutamic acid 219 is critical for the thermostability of a truncated α-amylase from alkaliphilic and thermophilic Bacillus sp. strain TS-23 - Long-Liu Lin; Jai-Shin Liu; Wen-Ching Wang; Szu-Han Chen; Chih-Chen Huang; Huei-Fen Lo (World Journal of Microbiology and Biotechnology, 2008)

Antioxidant activity of polar lichens from King George Island (Antarctica) - Babita Paudel; Hari Datta Bhattarai; Jin Sung Lee; Soon Gyu Hong; Hyun Woung Shin; Joung Han Yim (Polar Biology, 2008)

Perfluorooctanoic acid-induced hepatic toxicity following 21-day oral exposure in mice - Hee-Young Son; Sang-Hyun Kim; Hong-In Shin; Han Ik Bae; Jae-Ho Yang (Archives of Toxicology, 2008)

Expressional characterization of dehydroascorbate reductase cDNA in transgenic potato plants - Young-Min Goo; Hyun Jin Chun; Tae-Won Kim; Cheol-Ho Lee; Mi-Jeong Ahn; Shin-Chul Bae; Kang-Jin Cho; Jae-An Chun; Chung-Han Chung; Shin-Woo Lee (Journal of Plant Biology, 2008)

Mercury-tolerant Transgenic Poplars Expressing Two Bacterial Mercury-metabolizing Genes - Young Im Choi; Eun Woon Noh; Hyo Shin Lee; Mu Seok Han; Jae Soon Lee; Kwan Sam Choi (Journal of Plant Biology, 2007)

15-Deoxy-Δ12,14-prostaglandin J2 (15d-PGJ2) sensitizes human leukemic HL-60 cells to tumor necrosis factor-related apoptosis-inducing ligand (TRAIL)-induced apoptosis through Akt downregulation - Hoon Han; Sung-Won Shin; Chi-Yeon Seo; Hyuk-Chan Kwon; Jin-Yeong Han; In-Hoo Kim; Jong-Young Kwak; Joo-In Park (Apoptosis, 2007)

Polymorphism and Genomic Structure of the A+T-Rich Region of Mitochondrial DNA in the Oriental Mole Cricket, Gryllotalpa Orientalis (Orthoptera: Gryllotalpidae) - Iksoo Kim; So Young Cha; Mi Ae Kim; Young Shin Lee; Kwang Sik Lee; Yong Soo Choi; Jae Sam Hwang; Byung Rae Jin; Yeon Soo Han (Biochemical Genetics, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Molecular identification and characterization of the tomato flagellin receptor LeFLS2, an orthologue of Arabidopsis FLS2 exhibiting characteristically different perception specificities - Silke Robatzek; Pascal Bittel; Delphine Chinchilla; Petra Köchner; Georg Felix; Shin-Han Shiu; Thomas Boller (Plant Molecular Biology, 2007)

OECD validation of the rodent Hershberger assay using three reference chemicals; 17α-methyltestosterone, procymidone, and p,p′-DDE - Jae-Ho Shin; Hyun Ju Moon; Il Hyun Kang; Tae Sung Kim; Su Jung Lee; Ji Youn Ahn; Hoon Bae; Eui Bae Jeung; Soon Young Han (Archives of Toxicology, 2007)

A peroxisome-proliferator activated receptor-γ ligand could regulate the expression of leptin receptor on human hepatic stellate cells - Jung Il Lee; Yong-Han Paik; Kwan Sik Lee; Jin Woo Lee; Yong Soo Kim; Seok Jeong; Kye Sook Kwon; Dong Haeng Lee; Hyung Gil Kim; Yong Woon Shin; Min Ah Kim (Histochemistry and Cell Biology, 2007)

Regional gravity modeling in terms of spherical base functions - Michael Schmidt; Martin Fengler; Torsten Mayer-Gürr; Annette Eicker; Jürgen Kusche; Laura Sánchez; Shin-Chan Han (Journal of Geodesy, 2007)

Comparative expression and characterization of dehydroascorbate reductase cDNA from transformed sesame hairy roots using real-time RT-PCR - Jae An Chun; Jee Young Seo; Mi Ok Han; Jin Woo Lee; Young Byung Yi; Gun Yong Park; Shin Woo Lee; Shin Chul Bae; Kang Jin Cho; Chung Han Chung (Journal of Plant Biology, 2006)

Repeated 28-day oral toxicity study of ketoconazole in rats based on the draft protocol for the “Enhanced OECD Test Guideline No. 407” to detect endocrine effects - Jae-Ho Shin; Hyun Ju Moon; Il Hyun Kang; Tae Sung Kim; In Young Kim; In Sook Park; Hyung Sik Kim; Eui Bae Jeung; Soon-Young Han (Archives of Toxicology, 2006)

Novel calcium-binding GTPase (AtCBG) involved in ABA-mediated salt stress signaling in Arabidopsis - Kandakumar Jayasekaran; Kyung-Nam Kim; Munusamy Vivekanandan; Jeong Sheop Shin; Sung Han Ok (Plant Cell Reports, 2006)

Using canopy reflectance and partial least squares regression to calculate within-field statistical variation in crop growth and nitrogen status of rice - Hung T. Nguyen; Jun Han Kim; Anh T. Nguyen; Lan T. Nguyen; Jin Chul Shin; Byun-Woo Lee (Precision Agriculture, 2006)

Seed-specific expression of sesame microsomal oleic acid desaturase is controlled by combinatorial properties between negative cis-regulatory elements in the SeFAD2 promoter and enhancers in the 5′-UTR intron - Mi Jung Kim; Heeja Kim; Jeong Sheop Shin; Chung-Han Chung; John B. Ohlrogge; Mi Chung Suh (Molecular Genetics and Genomics, 2006)

Repeated 28-day oral toxicity study of vinclozolin in rats based on the draft protocol for the “Enhanced OECD Test Guideline No. 407” to detect endocrine effects - Jae-Ho Shin; Hyun Ju Moon; Tae Sung Kim; Il Hyun Kang; Ho Yeon Ki; Kwang Sik Choi; Soon Young Han (Archives of Toxicology, 2006)

Morphology and Molecular Data for Antarctic Cryophilic Microalga, Porosira pseudodenticulata - Woong-Sic Jung; Hyoung-Min Joo; Sung-Soo Hong; Jae-Shin Kang; Han-Gu Choi; Sung-Ho Kang (Algae, 2006)

Proteome analysis of gametophores identified a metallothionein involved in various abiotic stress responses in Physcomitrella patens - Sung Hyun Cho; Quoc Truong Hoang; Yoon Young Kim; Hyun Young Shin; Sung Han Ok; Jung Myung Bae; Jeong Sheop Shin (Plant Cell Reports, 2006)

High glucose and angiotensin II increase β1 integrin and integrin-linked kinase synthesis in cultured mouse podocytes - Sang Youb Han; Young Sun Kang; Yi Hwa Jee; Kum Hyun Han; Dae Ryong Cha; Shin Wook Kang; Dae Suk Han (Cell and Tissue Research, 2006)

An efficient and novel plant selectable marker based on organomercurial resistance - Young Im Choi; Eun Woon Noh; Hyo Shin Lee; Mu Seok Han; Jae Soon Lee; Kwan Sam Choi (Journal of Plant Biology, 2005)

Transgenic watermelon rootstock resistant to CGMMV (cucumber green mottle mosaic virus) infection - Sang Mi Park; Jung Suk Lee; Sung Jegal; Bo Young Jeon; Min Jung; Yoon Sik Park; Sang Lyul Han; Yoon Sup Shin; Nam Han Her; Jang Ha Lee; Mi Yeon Lee; Ki Hyun Ryu; et al. (Plant Cell Reports, 2005)

Overexpression of human erythropoietin (EPO) affects plant morphologies: retarded vegetative growth in tobacco and male sterility in tobacco and Arabidopsis - Ban Yoon Cheon; Hae Jin Kim; Kyung Hee Oh; Sung Chul Bahn; Ji Hoon Ahn; Jang Won Choi; Sung Han Ok; Jung Myung Bae; Jeong Sheop Shin (Transgenic Research, 2004)

High dose of glucose promotes chondrogenesis via PKC? and MAPK signaling pathways in chick mesenchymal cells - Yong-Su Han; Ok-Sun Bang; Eun-Jung Jin; Jae-Han Park; Jong-Kyung Sonn; Shin-Sung Kang (Cell and Tissue Research, 2004)

Mutational analysis of OGG1, MYH, MTH1 in FAP, HNPCC and sporadic colorectal cancer patients: R154H OGG1 polymorphism is associated with sporadic colorectal cancer patients - I.-J. Kim; J.-L. Ku; H. C. Kang; J.-H. Park; K.-A. Yoon; Y. Shin; H.-W. Park; S. G. Jang; S.-K. Lim; S. Y. Han; Y.-K. Shin; M. R. Lee; et al. (Human Genetics, 2004)

Expression of the Bovine Growth Hormone Alters the Root Morphology in Transgenic Tobacco Plants - Kyunghee Oh; Ban Yoon Cheon; Sung Hyun Cho; Hoang Quoc Truong; Sung Han Ok; Ji Ung Jeung; Jang Won Choi; Jeong Sheop Shin (Transgenic Research, 2003)

Isolation and characterization of a myo-inositol 1-phosphate synthase cDNA from developing sesame (Sesamum indicum L.) seeds: functional and differential expression, and salt-induced transcription during germination - Jae-An Chun; Un-Ho Jin; Jin-Woo Lee; Young-Byung Yi; Nam-In Hyung; Myung-Hwa Kang; Jae-Ho Pyee; Mi Suh; Churl-Whan Kang; Hong-Yeol Seo; Shin-Woo Lee; Chung-Han Chung (Planta, 2003)

Characteristics of aroma-active compounds in the pectin-elicited suspension culture of Zanthoxylum piperitum (prickly ash) - Tae Hwan Kim; Tae Ho Kim; Joong Han Shin; Eun Jeong Yu; Young-Suk Kim; Hyong Joo Lee (Biotechnology Letters, 2002)

The Potential use of a Viral Coat Protein Gene as a Transgene Screening Marker and Multiple Virus Resistance of Pepper Plants Coexpressing Coat Proteins of Cucumber Mosaic Virus and Tomato Mosaic Virus - Ryoung Shin; Jung-Heon Han; Gil-Je Lee; Kyung-Hee Peak (Transgenic Research, 2002)

A shoot regeneration protocol effective on diverse genotypes of sunflower (Helianthus annuus L.) - Dong-Ho Shin; Jin Sook Kim; In Jeong Kim; Jaemo Yang; Soo Kyung Oh; Gab Chae Chung; Kyung-Hwan Han (In Vitro Cellular & Developmental Biology - Plant, 2000)

Production of biologically active human granulocyte colony stimulating factor in the milk of transgenic goat - Jung Ho Ko; Chul-Sang Lee; Kui Hyun Kim; Myung-Geol Pang; Ja Shin Koo; Nanzhu Fang; Deog-Bon Koo; Keon Bong Oh; Woo-Sik Youn; Guo Dong Zheng; Jung Sun Park; Sun Jung Kim; et al. (Transgenic Research, 2000)

Embryo lethality and teratogenicity of a new fluoroquinolone antibacterial DW-116 in rats - Jong-Choon Kim; Hyo-In Yun; Ho-Chul Shin; Sang-Seop Han; Moon-Koo Chung (Archives of Toxicology, 2000)

Genetic transformation of Cymbidium orchid by particle bombardment - J. Yang; H.-J. Lee; D. H. Shin; S. K. Oh; J. H. Seon; K. Y. Paek; K.-H. Han (Plant Cell Reports, 1999)

Improved menthol production from chitosan-elicited suspension culture of Mentha piperita - Jun Hyong Chang; Joong Han Shin; In Sik Chung; Hyong Joo Lee (Biotechnology Letters, 1998)

Expression and secretion of Clostridium thermocellum endoglucanase A gene (celA) in different Saccharomyces cerevisiae strains - Dae-Kyun Chung; Dong-Ha Shin; Byung-Woo Kim; Jae-Kook Nam; In-Seob Han; Soo-Wan Nam (Biotechnology Letters, 1997)

210 Pb-derived sediment accumulation rates in the southwestern East Sea (Sea of Japan) - G. H. Hong; S. H. Kim; C. S. Chung; D.-J. Kang; D.-H. Shin; H. J. Lee; S.-J. Han (Geo-Marine Letters, 1997)

Partial sequence analysis of randomly selected watermelon [Citrullus lanantus (Thunb.) Mansf.] cDNA clones - Ok Sung Han; Jeong Sheop Shin; Young Soo Chung; Hyok Ji Kwon (Journal of Plant Biology, 1997)